A spinel glass-ceramic, chemically strengthened glass-ceramic and applications thereof
By adjusting the composition and heat treatment process of spinel microcrystalline glass and combining chemical strengthening treatment, the problem of insufficient impact and drop resistance of spinel microcrystalline glass in the prior art is solved, high intrinsic strength and excellent stress characteristics are achieved, and the preparation cost is reduced.
Patent Information
- Application Number
- CN202310389939.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-12
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-04-12
AI Technical Summary
The prior art is difficult to obtain spinel microcrystalline glass with high stress layer depth and excellent deep stress characteristics, resulting in insufficient impact and drop resistance.
By adjusting the composition of spinel microcrystalline glass, optimizing the amount of oxides, combined with heat treatment technology, spinel microcrystalline glass with specific structure and high intrinsic strength is prepared, and excellent surface stress characteristics and deep stress characteristics are obtained through chemical strengthening treatment.
The high intrinsic strength and excellent anti-fall impact performance of spinel microcrystalline glass are achieved, reducing the preparation cost and avoiding the use of high-cost lithium ions.
Smart Images

Figure CN118270985B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of glass-ceramics, and in particular to spinel glass-ceramics, chemically strengthened glass-ceramics and applications thereof. Background Art
[0002] Glass-ceramics, also known as glass ceramics, is a type of solid composite material that contains both glass phase and microcrystalline phase and is prepared by targeted controlled heat treatment of substrate glass. The crystalline phase precipitated inside the glass-ceramics can hinder the expansion of microcracks, thereby improving the fragility of the substrate glass to a certain extent. Compared with ordinary glass materials, glass-ceramics have better mechanical properties, and therefore, glass-ceramics have become a better choice for protective back panels of portable electronic devices. Among the many glass-ceramics, spinel glass-ceramics with spinel as the main crystal phase has gradually attracted the attention of people in the industry because of its high Young's modulus and shear modulus.
[0003] For the protective backplane of portable electronic devices, due to its small thickness, it needs to have higher stress performance, such as higher stress layer depth, excellent surface stress characteristics and excellent deep stress characteristics, in order to obtain high mechanical strength. Among them, higher stress layer depth and excellent deep stress characteristics are necessary conditions for the backplane glass to obtain excellent impact resistance and excellent drop resistance. Therefore, how to obtain microcrystalline glass with higher stress layer depth and excellent deep stress characteristics has become a technical problem that needs to be solved urgently. Summary of the invention
[0004] The purpose of the embodiments of the present invention is to provide a spinel glass-ceramic, a chemically strengthened glass-ceramic and their applications. The inventors continuously optimized the composition, adjusted the amount of each oxide in the composition, and took into account the melting effect, stress effect, optical effect and mechanical properties, and finally developed a spinel glass-ceramic with a specific structure, good overall uniformity and high intrinsic strength. Not only is the preparation cost of the spinel glass-ceramic lower than that of the existing lithium-containing spinel glass-ceramic, but the spinel glass-ceramic can also be chemically strengthened to obtain chemically strengthened glass-ceramic with excellent surface stress characteristics, higher stress layer depth and excellent deep stress characteristics. The specific technical scheme is as follows:
[0005] The first aspect of the present invention provides a spinel glass-ceramic, wherein the spinel glass-ceramic includes a main crystalline phase (Zn, Mg)Al 2 O 4 ; The spinel glass-ceramics with a thickness of 0.7 mm has an average transmittance in the visible light range of less than or equal to 70.00%;
[0006] Expressed in terms of molar percentage of oxides, the spinel glass-ceramics comprises: SiO2 38.00mol%~48.30mol%, Al 2 O 3 25.50mol%~30.00mol%, MgO 5.00mol%~8.00mol%, ZnO8.00mol%~14.00mol%, ZrO 2 3.00 mol%~5.00 mol%, Na 2 O 7.20mol%~14.00mol%, K 2 O 0.00 mol%~2.00 mol%, B 2 O 3 3.00 mol%~8.00 mol%, Y 2 O 3 0.00mol%~1.00mol%, BaO0.00mol%~2.10mol%; the composition of the spinel glass-ceramics does not include Li 2 O.
[0007] In some embodiments of the present invention, the composition of the spinel glass-ceramics satisfies, based on the molar percentage of each oxide in the spinel glass-ceramics composition:
[0008] The value of X is calculated based on the following formula (1), 30.00%≤X≤50.00%,
[0009] X = 2.1 × (Al 2 O 3 -MgO-ZnO) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O+K 2 O+B 2 O 3 )×100% Formula (1);
[0010] and / or,
[0011] The value of Y is calculated based on the following formula (2): 60.00%≤Y≤80.00%,
[0012] Y=(2.7×Na 2 O+1.8×(Al 2 O 3 -MgO-ZnO)) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O+K 2 O+B 2 O3 )×100% Formula (2).
[0013] In some embodiments of the present invention, the composition of the spinel glass-ceramics satisfies, based on the molar percentage of each oxide in the spinel glass-ceramics composition: A value calculated based on the following formula (3), A≤0.18, preferably A value is 0.05 to 0.15,
[0014] A=0.65×Al 2 O 3 +3.5×ZrO 2 -0.8×Na 2 O-2.5×B 2 O 3 Formula (3).
[0015] In some embodiments of the present invention, the composition of the spinel glass-ceramics further includes: 0 mol% to 5.00 mol% of a colorant;
[0016] Expressed in terms of molar percentage of oxides, the colorant includes: NiO 0.00mol% to 4.00mol%, Ni 2 O 3 0.00mol%~2.00mol%, Pr 2 O 5 0.00mol%~2.00mol%, CoO 0.00mol%~2.00mol%, Co 2 O 3 0.00mol%~1.00mol%,Cu 2 O 0.00mol%~2.20mol%, CeO 2 0.00mol%~2.00mol%,Fe 2 O 3 0.00mol%~3.50mol%, MnO 2 0.00mol%~4.00mol%, Er 2 O 3 0.00mol%~1.00mol%, Nd 2 O 3 0.00mol%~2.00mol%.
[0017] In some embodiments of the present invention, the spinel glass-ceramics does not include TiO 2 ; and / or, the composition of the spinel glass-ceramics does not include BaO.
[0018] In some embodiments of the present invention, the spinel glass-ceramics further comprises a secondary crystalline phase, wherein the secondary crystalline phase comprises tetragonal ZrO2 , baddeleyite, quartz, mullite and cordierite.
[0019] In some embodiments of the present invention, the spinel glass-ceramics has a degree of crystallinity greater than or equal to 30.00wt%, preferably a degree of crystallinity of 30.00wt% to 50.00wt%, and more preferably a degree of crystallinity of 35.00wt% to 50.00wt%; and / or, the spinel glass-ceramics has an average grain size of 10.0nm to 1000.0nm, preferably 10.0nm to 500.0nm, and more preferably 10.0nm to 100.0nm.
[0020] In the present invention, when testing the crystallinity of spinel glass-ceramics, the spinel glass-ceramics are first ground into fine powder with a maximum particle size of less than 75 μm, and then the XRD diffraction data of the fine powder is obtained by testing, and then the XRD diffraction data is fitted and calculated by analysis software to obtain the crystalline phase content of the glass-ceramics. The above-mentioned analysis software may include but is not limited to Gsas, Fullprof, Maud, Jade, etc.
[0021] In some embodiments of the present invention, the haze of the 0.7 mm thick spinel glass-ceramics is 60.00% to 99.90%.
[0022] In some embodiments of the present invention, the spinel glass-ceramic comprises a color presented in CIE LAB color space coordinates, measured from the reflectance spectrum using a spectrophotometer with mirror reflection at an observation angle of 10° and CIE illuminant D65, and the L value, a value and b value satisfy: the L value is 20.00 to 99.99; the a value is -5.00 to +25.00; and the b value is -50.00 to +5.00.
[0023] In some embodiments of the present invention, the Young's modulus of the spinel glass-ceramics is greater than or equal to 100 GPa, preferably 100 GPa to 140 GPa, and more preferably 110 GPa to 140 GPa.
[0024] In some embodiments of the present invention, in the spinel glass-ceramics,
[0025] SiO 2 The molar percentage is 38.00 mol% to 48.00 mol%, preferably 38.00 mol% to 45.00 mol%; and / or,
[0026] The molar percentage of MgO is 5.00 mol% to 7.00 mol%, preferably 5.00 mol% to 6.50 mol%; and / or,
[0027] The molar percentage of ZnO is 8.00 mol% to 13.00 mol%, preferably 8.50 mol% to 11.00 mol%; and / or,
[0028] ZrO 2 The molar percentage is 3.00 mol% to 4.50 mol%, preferably 3.00 mol% to 4.00 mol%; and / or,
[0029] Na 2 The molar percentage of O is 7.20 mol% to 13.00 mol%, preferably 7.20 mol% to 12.50 mol%; and / or,
[0030] K 2 The molar percentage of O is 0.00 mol% to 1.00 mol%; and / or,
[0031] B 2 O 3 The molar percentage is 3.00mol% to 7.50mol%; and / or,
[0032] The molar percentage of BaO is 0.00 mol% to 1.80 mol%, preferably 0.00 mol% to 1.50 mol%.
[0033] A second aspect of the present invention provides a method for preparing the spinel glass-ceramics in any of the aforementioned embodiments, comprising the following steps:
[0034] (1) preparing a substrate glass; the composition of the substrate glass, expressed in terms of molar percentage of oxides, includes: SiO 2 38.00mol%~48.30mol%, Al 2 O 3 25.50mol%~30.00mol%, MgO 5.00mol%~8.00mol%, ZnO 8.00mol%~14.00mol%, ZrO 2 3.00 mol%~5.00 mol%, Na 2 O 7.20mol%~14.00mol%, K 2 O 0.00mol%~2.00mol%, B 2 O 3 3.00 mol%~8.00 mol%, Y 2 O 3 0.00mol%~1.00mol%, BaO 0.00mol%~2.10mol%; the composition of the substrate glass does not include Li 2 O;
[0035] (2) Preparation of glass-ceramics: The substrate glass obtained in step (1) is heat-treated to obtain the spinel glass-ceramics in any of the above embodiments.
[0036] In some embodiments of the present invention, in step (2), the heat treatment includes nucleation treatment and crystallization treatment; wherein: the temperature of the nucleation treatment is 600°C to 850°C, preferably 650°C to 850°C; the nucleation treatment time is 0h to 72h, preferably 0h to 24h, more preferably 0h to 8h; the crystallization treatment temperature is 850°C to 1100°C, the crystallization treatment time is 0.1h to 72h, preferably 0.1h to 24h, more preferably 4h to 8h; and / or,
[0037] In step (2), when heat treatment is performed, the heating rate is controlled to be 5K / min to 15K / min, preferably 5K / min to 10K / min.
[0038] In some embodiments of the present invention, the composition of the substrate glass satisfies the following conditions, based on the molar percentage of each oxide in the substrate glass composition:
[0039] The value of X is calculated based on the following formula (1), 30.00%≤X≤50.00%,
[0040] X = 2.1 × (Al 2 O 3 -MgO-ZnO) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O+K 2 O+B 2 O 3 )×100% Formula (1);
[0041] and / or,
[0042] The value of Y is calculated based on the following formula (2): 60.00%≤Y≤80.00%,
[0043] Y=(2.7×Na 2 O+1.8×(Al 2 O 3 -MgO-ZnO)) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O+K 2 O+B 2 O 3 )×100% Formula (2);
[0044] and / or,
[0045] The value of A is calculated based on the following formula (3), A≤0.18, and the preferred value of A is 0.05 to 0.15.
[0046] A=0.65×Al 2 O 3 +3.5×ZrO 2 -0.8×Na 2 O-2.5×B 2 O 3 Formula (3);
[0047] and / or,
[0048] The composition of the substrate glass further includes: 0 mol% to 5.00 mol% of colorant; expressed in terms of molar percentage of oxides, the colorant includes: NiO 0.00 mol% to 4.00 mol%, Ni 2 O 3 0.00mol%~2.00mol%, Pr 2 O 5 0.00mol%~2.00mol%, CoO 0.00mol%~2.00mol%, Co 2 O 3 0.00mol%~1.00mol%,Cu 2 O0.00mol%~2.20mol%, CeO 2 0.00mol%~2.00mol%,Fe 2 O 3 0.00mol%~3.50mol%, MnO 2 0.00mol%~4.00mol%, Er 2 O 3 0.00mol%~1.00mol%, Nd 2 O 3 0.00mol%~2.00mol%;
[0049] and / or,
[0050] The composition of the substrate glass does not include TiO 2 ; and / or, the composition of the substrate glass does not include BaO.
[0051] The third aspect of the present invention provides a chemically strengthened glass-ceramic, wherein the chemically strengthened glass-ceramic is obtained by subjecting the spinel glass-ceramic in any of the aforementioned embodiments to chemical strengthening treatment, or by subjecting the spinel glass-ceramic prepared by the preparation method in any of the aforementioned embodiments to chemical strengthening treatment.
[0052] In some embodiments of the present invention, the salt bath for chemical strengthening treatment is a molten salt containing potassium salt, and the potassium salt includes one or more of potassium nitrate, potassium sulfate, and potassium carbonate, preferably potassium nitrate; the temperature of the salt bath for chemical strengthening treatment is 380°C to 600°C, preferably 400°C to 550°C, and more preferably 400°C to 500°C; the time of the chemical strengthening treatment is 1h to 48h, preferably 6h to 24h, and more preferably 12h to 24h.
[0053] In some embodiments of the present invention, in the chemically strengthened glass-ceramics, along the thickness direction of the chemically strengthened glass-ceramics, the depth from any surface of the chemically strengthened glass-ceramics to a position close to the surface having the same potassium concentration as that at the center of the chemically strengthened glass-ceramics is ≥ 0.07t, preferably 0.07t to 0.22t, further preferably 0.10t to 0.22t, and more preferably 0.13t to 0.22t, where t is the thickness of the chemically strengthened glass-ceramics.
[0054] In some embodiments of the present invention, the surface K of the chemically strengthened microcrystalline glass 2 The O concentration is ≥ 9.00 wt%, preferably 9.00 wt% to 16.00 wt%.
[0055] In some embodiments of the present invention, a 0.7 mm thick chemically strengthened glass-ceramics is subjected to a drop resistance test using 120-grit sandpaper, and the average sandpaper resistance drop height of the chemically strengthened glass-ceramics is greater than or equal to 1.80 m, preferably greater than or equal to 1.90 m, and more preferably greater than or equal to 2.00 m.
[0056] In some embodiments of the present invention, a 0.7 mm thick chemically strengthened glass-ceramics is subjected to a 2.5 m drop test using 120-grit sandpaper, and the drop test pass rate of the chemically strengthened glass-ceramics is greater than or equal to 50%, preferably greater than or equal to 60%.
[0057] A fourth aspect of the present invention provides a glass device, which is made of the spinel glass-ceramic in any of the foregoing embodiments, or made of the chemically strengthened glass-ceramic in any of the foregoing embodiments.
[0058] A fifth aspect of the present invention provides an electronic device comprising the spinel glass-ceramic in any of the foregoing embodiments, or comprising the chemically strengthened glass-ceramic in any of the foregoing embodiments.
[0059] A sixth aspect of the present invention provides a substrate glass, which can be used to prepare the spinel glass-ceramics in any of the above embodiments; the composition of the substrate glass, expressed in terms of molar percentage of oxides, includes: SiO 238.00mol%~48.30mol%, Al 2 O 3 25.50mol%~30.00mol%, MgO 5.00mol%~8.00mol%, ZnO 8.00mol%~14.00mol%, ZrO 2 3.00 mol%~5.00 mol%, Na 2 O 7.20mol%~14.00mol%, K 2 O 0.00mol%~2.00mol%, B 2 O 3 3.00 mol%~8.00 mol%, Y 2 O 3 0.00mol%~1.00mol%, BaO 0.00mol%~2.10mol%; the composition of the substrate glass does not include Li 2 O.
[0060] In some embodiments of the present invention, the composition of the substrate glass satisfies the following conditions, based on the molar percentage of each oxide in the substrate glass composition:
[0061] The value of X is calculated based on the following formula (1), 30.00%≤X≤50.00%,
[0062] X = 2.1 × (Al 2 O 3 -MgO-ZnO) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O+K 2 O+B 2 O 3 )×100% Formula (1);
[0063] and / or,
[0064] The value of Y is calculated based on the following formula (2): 60.00%≤Y≤80.00%,
[0065] Y=(2.7×Na 2 O+1.8×(Al 2 O 3 -MgO-ZnO)) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O+K 2 O+B 2 O 3)×100% Formula (2);
[0066] and / or,
[0067] The value of A is calculated based on the following formula (3), A≤0.18, and the preferred value of A is 0.05 to 0.15.
[0068] A=0.65×Al 2 O 3 +3.5×ZrO 2 -0.8×Na 2 O-2.5×B 2 O 3 Formula (3);
[0069] and / or,
[0070] The composition of the substrate glass further includes: 0 mol% to 5.00 mol% of colorant; expressed in terms of molar percentage of oxides, the colorant includes: NiO 0.00 mol% to 4.00 mol%, Ni 2 O 3 0.00mol%~2.00mol%, Pr 2 O 5 0.00mol%~2.00mol%, CoO 0.00mol%~2.00mol%, Co 2 O 3 0.00mol%~1.00mol%,Cu 2 O0.00mol%~2.20mol%, CeO 2 0.00mol%~2.00mol%,Fe 2 O 3 0.00mol%~3.50mol%, MnO 2 0.00mol%~4.00mol%, Er 2 O 3 0.00mol%~1.00mol%, Nd 2 O 3 0.00 mol% to 2.00 mol%; and / or,
[0071] The composition of the substrate glass does not include TiO 2 ; and / or, the composition of the substrate glass does not include BaO.
[0072] Beneficial effects of the present invention:
[0073] The spinel glass-ceramics provided by the present invention has high intrinsic strength, and can be chemically strengthened to obtain chemically strengthened glass-ceramics with excellent drop impact resistance, which can meet the use requirements of electronic equipment protective glass. The present invention adjusts the amount of each oxide in the composition so that the oxide components with specific contents cooperate with each other, thereby preparing a spinel glass-ceramics with a specific composition and structure. The spinel glass-ceramics of the present invention has a large number of main crystal phases (Zn, Mg)Al with high Young's modulus and shear modulus evenly distributed in a specific network structure. 2 O 4 While ensuring that the spinel glass-ceramics have high intrinsic strength, the ion exchange capacity of the spinel glass-ceramics is significantly improved, so that the spinel glass-ceramics can simultaneously obtain a higher compressive stress layer depth and excellent surface stress characteristics after chemical strengthening. The spinel glass-ceramics of the present invention can be processed by chemical strengthening to obtain chemically strengthened glass-ceramics having both excellent surface stress characteristics and excellent deep stress characteristics. The high intrinsic strength combined with the excellent surface stress characteristics and the excellent deep stress characteristics endows the chemically strengthened glass-ceramics with excellent mechanical strength, and especially gives the chemically strengthened glass-ceramics excellent drop impact resistance.
[0074] The spinel glass-ceramics provided by the present invention does not need to use expensive lithium, and can also obtain chemically strengthened glass-ceramics with excellent impact resistance and excellent drop resistance through chemical strengthening. Compared with the existing lithium-containing spinel glass-ceramics, the spinel glass-ceramics provided by the present invention has better economic benefits.
[0075] Of course, it is not necessary to achieve all of the advantages described above at the same time to implement any product or method of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0077] Figure 1 The DSC test spectrum of the substrate glass in Example 1 of the present invention;
[0078] Figure 2 is the X-ray diffraction pattern of the spinel glass-ceramics in Example 1 of the present invention;
[0079] Figure 3 is the X-ray diffraction pattern of the spinel glass-ceramics in Example 6 of the present invention;
[0080] Figure 4 is the X-ray diffraction pattern of the spinel glass-ceramics in Example 7 of the present invention;
[0081] Figure 5a This is the appearance of the heat-treated glass-ceramics in Comparative Example 4;
[0082] Figure 5b This is an appearance diagram of the spinel glass-ceramics in Example 3;
[0083] Figure 6 Graphs showing transmittance of the spinel glass-ceramics in Examples 1, 2 and 7 in the visible light band;
[0084] Figure 7 is a graph showing the relationship between the content of K and Na elements and the depth below the surface in the chemically strengthened glass-ceramics in Example 21;
[0085] Figure 8 This is a graph showing the relationship between the K and Na element contents in the chemically strengthened glass-ceramics in Example 24 and the depth below the surface. DETAILED DESCRIPTION
[0086] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field based on the present invention belong to the scope of protection of the present invention.
[0087] Explanation of terms
[0088] Base glass: refers to glass that has not been subjected to nucleation treatment, crystallization treatment, and strengthening treatment.
[0089] Glass-ceramics: also known as glass ceramics, is a type of solid composite material that contains both glass phase and microcrystalline phase and is prepared by targeted controlled heat treatment of the base glass. The microcrystalline phase here is also called crystal phase, crystalline phase, or crystal phase in other materials.
[0090] Chemically strengthened microcrystalline glass: refers to the solid composite material obtained after microcrystalline glass is chemically strengthened. It should be understood that when high-temperature chemical strengthening treatment or high-temperature ion exchange process is carried out, the alkali metal ions with large ionic radius (such as potassium ions and sodium ions) in the salt bath or molten salt (molten salt) will replace the alkali metal ions with small ionic radius (such as sodium ions and lithium ions) in the microcrystalline glass, thereby generating an exchange ion volume difference, and generating high to low compressive stress from the surface to the inside of the microcrystalline glass, hindering and delaying the expansion of microcracks, so as to achieve the purpose of improving the mechanical strength of the microcrystalline glass.
[0091] Nucleation temperature: refers to the temperature at which crystal nuclei are formed.
[0092] Crystallization temperature: refers to the temperature at which the target crystal growth rate can be controlled.
[0093] Transmittance: When light of a certain wavelength is irradiated onto the glass surface, the light will be reflected, absorbed and transmitted. The ratio of the intensity of the transmitted part to the intensity of the incident light is the transmittance.
[0094] In the present invention, the average transmittance of glass-ceramics in the visible light range refers to the average transmittance of glass-ceramics measured under light with a wavelength in the range of 360nm to 740nm. The present invention uses a Konica Minolta spectrophotometer CM-3600A to test the average transmittance of glass-ceramics under light with a wavelength in the range of 360nm to 740nm.
[0095] Crystallinity: refers to the percentage of the total mass of the crystalline phase / crystals in the microcrystalline glass to the mass of the microcrystalline glass.
[0096] Haze (C) refers to the percentage of the transmitted light intensity that deviates from the incident light by more than 2.5° to the total transmitted light intensity. The haze in the present invention is the haze value measured by a Konica Minolta spectrophotometer CM-3600A under standard C light source.
[0097] L value: In the present invention, the L value is the specular reflection light (SCI) L value, which indicates the brightness of the material. A positive L value indicates whiteness, and a negative L value indicates blackness.
[0098] a value: In the present invention, the a value is the specular reflection light (SCI) a value, which represents the red-green value of the material. A positive a value indicates that the material is reddish, and a negative a value indicates that the material is greenish.
[0099] b value: In the present invention, the b value is the specular reflection light (SCI) b value, which represents the yellow-blue value of the material. A positive b value indicates that the material is yellowish, and a negative b value indicates that the material is blueish.
[0100] In the present invention, the L value, a value, and b value of the microcrystalline glass are measured using a Konica Minolta spectrophotometer CM-3600A.
[0101] At present, in order to make spinel glass-ceramics meet the requirements of protective back panels of portable electronic devices, the prior art usually introduces alkali metal oxides (such as Li 2 O、Na 2 O), by chemically strengthening the spinel glass-ceramics to obtain chemically strengthened glass-ceramics with stress characteristics.
[0102] In the prior art, a common method is to introduce a large amount of lithium ions into the composition of spinel glass-ceramics and use sodium-lithium exchange to achieve chemical strengthening and toughening of spinel glass-ceramics, so that the spinel glass-ceramics can obtain higher stress performance and thus obtain excellent drop resistance. 2 O is expensive, and the large-scale use of lithium oxide will lead to excessively high costs for spinel glass-ceramics. Another common method is to introduce sodium ions into the composition of spinel glass-ceramics and use potassium-sodium exchange to achieve chemical strengthening and toughening of spinel glass-ceramics, but the existing technology using this method is currently unable to enable spinel glass-ceramics to obtain excellent drop impact resistance. For example, the invention application CN111908793A discloses a glass ceramic with a spinel crystal phase, the components of which contain SiO 2 50mol%~70mol%Al 2 O 3 5mol%~21mol%Na 2 O 6mol%~21mol%, ZnO 2mol%~12mol%, TiO 2 0.5mol%~10mol%, MgO 0mol%~10mol%. A large amount of Na 2 However, after chemical strengthening, the glass ceramic can only obtain a compressive stress layer depth of no more than 40 μm, and the deep stress characteristics are poor. After a drop impact, it is very easy to break, and it is difficult to achieve an excellent drop impact resistance effect, and thus it is difficult to meet the drop impact resistance performance requirements of electronic equipment protective glass.
[0103] Based on the above problems, the inventors of the present invention have begun to work on developing spinel glass-ceramics that does not contain lithium and can obtain excellent stress properties through chemical strengthening.
[0104] In view of the technical problem in the prior art that even if a large amount of sodium ions are introduced into the composition of lithium-free spinel glass-ceramics, it is still impossible to obtain excellent drop impact resistance after chemical strengthening and toughening. After in-depth research, the inventors found that the main reason is that the composition and structure of the sodium-containing lithium-free spinel glass-ceramics in the prior art make it difficult to obtain a deeper compressive stress layer after chemical strengthening, that is, the depth of the compressive stress layer obtained by the existing sodium-containing lithium-free spinel glass-ceramics after chemical strengthening is not high enough, resulting in the inability to obtain excellent deep stress characteristics, which in turn causes it to be easily broken after a drop impact and cannot achieve the ideal drop impact resistance effect.
[0105] In view of this, the inventors have conducted a lot of research and provided a spinel glass-ceramic, a chemically strengthened glass-ceramic and applications thereof. By using the spinel glass-ceramic provided by the present invention, a chemically strengthened glass-ceramic having both excellent surface stress characteristics and excellent deep stress characteristics can be prepared, thereby ensuring that the chemically strengthened glass-ceramic has excellent drop impact resistance.
[0106] The first aspect of the present invention provides a spinel glass-ceramic, wherein the spinel glass-ceramic includes a main crystalline phase (Zn, Mg)Al 2 O 4 ; (Zn, Mg)Al 2 O 4 It is a zinc-magnesium spinel crystal, or also called a zinc-magnesium spinel solid solution, which is a solid solution formed by zinc-aluminum spinel and magnesium-aluminum spinel; the average transmittance of 0.7mm thick spinel glass-ceramics in the visible light range is less than or equal to 70.00%;
[0107] Expressed as molar percentage of oxides, the composition of spinel glass-ceramics includes: SiO 2 38.00mol%~48.30mol%, Al 2 O 3 25.50mol%~30.00mol%, MgO 5.00mol%~8.00mol%, ZnO 8.00mol%~14.00mol%, ZrO 2 3.00 mol%~5.00 mol%, Na 2 O 7.20mol%~14.00mol%, K 2 O 0.00 mol%~2.00 mol%, B 2 O 3 3.00 mol%~8.00 mol%, Y 2 O 3 0.00mol%~1.00mol%, BaO0.00mol%~2.10mol%; the composition of spinel glass-ceramics does not include Li 2 O. In the present invention, the visible light band refers to light in the band of 360nm to 740nm.
[0108] In some embodiments of the present invention, the average transmittance of 0.7 mm thick spinel glass-ceramics in the visible light range can be 0%, 5.00%, 10.00%, 15.00%, 20.00%, 25.00%, 30.00%, 35.00%, 40.00%, 45.00%, 50.00%, 55.00%, 60.00%, 65.00%, 70.00% or a value within the numerical range formed by any two of the above values as endpoints.
[0109] In some embodiments of the present invention, in the spinel glass-ceramics, SiO 2 The molar percentage of ZnO is 38.00mol% to 48.00mol%, preferably 38.00mol% to 45.00mol%; and / or, the molar percentage of MgO is 5.00mol% to 7.00mol%, preferably 5.00mol% to 6.50mol%; and / or, the molar percentage of ZnO is 8.00mol% to 13.00mol%, preferably 8.50mol% to 11.00mol%; and / or, the molar percentage of ZrO is 2 The molar percentage of Na is 3.00 mol% to 4.50 mol%, preferably 3.00 mol% to 4.00 mol%; and / or, Na 2 The molar percentage of O is 7.20 mol% to 13.00 mol%, preferably 7.20 mol% to 12.50 mol%; and / or, K 2 The molar percentage of O is 0.00 mol% to 1.00 mol%; and / or, B 2 O 3 The molar percentage of is 3.00 mol% to 7.50 mol%; and / or, the molar percentage of BaO is 0.00 mol% to 1.80 mol%, preferably 0.00 mol% to 1.50 mol%.
[0110] The inventors found that SiO 2 As a glass network forming oxide, it is an indispensable component of the spinel glass-ceramic network structure. 2 The addition of SiO can increase the stability and mechanical strength of the glass structure, but excessive SiO 2 It will increase the viscosity of the substrate glass, making it more difficult to melt the substrate glass, thereby reducing the formability of the substrate glass. Therefore, in the present invention, SiO 2 The content of is 38.00 mol% to 48.30 mol%, preferably 38.00 mol% to 48.00 mol%, and more preferably 38.00 mol% to 45.00 mol%. Within the above range, the strength and processing performance of the spinel glass-ceramics can be ensured, and the structural stability and formability of the spinel glass-ceramics can be ensured.
[0111] In some embodiments, SiO 2The content can be 38.00mol%, 39.00mol%, 40.00mol%, 41.00mol%, 42.00mol%, 43.00mol%, 44.00mol%, 45.00mol%, 46.00mol%, 47.00mol%, 48.00mol%, 48.30mol% or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the spinel glass-ceramics with the desired properties of the present invention can be obtained. In the present invention, "implementation method" is also "implementation scheme".
[0112] The inventors have found that in the formulation system of the present invention, Al 2 O 3 The appropriate addition of Al can not only promote the precipitation of the main crystal phase spinel, but also improve the ion exchange performance of spinel glass-ceramics and promote the ion exchange. 2 O 3 This will lead to a sharp increase in the difficulty of melting the substrate glass, and at the same time accelerate the crystallization rate of the substrate glass, making it easy for the substrate glass to crystallize and lose clarity during the normal cooling process of melting. 2 O 3 The content of is 25.50 mol% to 30.00 mol%, preferably 26.00 mol% to 28.50 mol%.
[0113] In some embodiments, Al 2 O 3 The content of can be 25.50mol%, 26.00mol%, 26.50mol%, 27.00mol%, 27.50mol%, 28.00mol%, 28.50mol%, 29.00mol%, 29.50mol%, 30.00mol% or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the spinel glass-ceramics with the desired properties of the present invention can be obtained.
[0114] The inventors have found that in the formula system of the present invention, MgO and ZnO are the main components of the spinel crystal phase. When an appropriate amount of MgO and ZnO are added, the precipitation of the main crystal phase spinel can be promoted, thereby ensuring that a spinel glass-ceramic with a high degree of crystallinity / crystal content is obtained, ensuring that the spinel glass-ceramic has a high intrinsic strength, and at the same time, it can also reduce the difficulty of melting the substrate glass to a certain extent. Therefore, in the present invention: in terms of mol%, the content of MgO is 5.00mol% to 8.00mol%, preferably 5.00mol% to 7.00mol%, and more preferably 5.00mol% to 6.50mol%; the content of ZnO is 8.00mol% to 14.00mol%, preferably 8.00mol% to 13.00mol%, and more preferably 8.50mol% to 11.00mol%.
[0115] In some embodiments, the content of MgO can be 5.00mol%, 5.50mol%, 6.00mol%, 6.50mol%, 7.00mol%, 7.50mol%, 8.00mol%, or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the spinel glass-ceramics with the desired properties of the present invention can be obtained.
[0116] In some embodiments, the content of ZnO can be 8.00mol%, 9.00mol%, 10.00mol%, 11.00mol%, 12.00mol%, 13.00mol%, 14.00mol%, or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the spinel glass-ceramics with the desired properties of the present invention can be obtained.
[0117] The inventors have found that in the formulation system of the present invention, ZrO 2 As a nucleating agent for spinel glass-ceramics, ZrO 2 First precipitated in the form of crystals, ZrO 2 The crystal becomes the nucleus for the subsequent growth of spinel crystals. 2 The content of ZrO not only affects the formation of the substrate glass, but also affects the crystal shape, crystal type and crystal size of the substrate glass during heat treatment (the heat treatment process here refers to the process of preparing microcrystalline glass from the substrate glass), thereby affecting the microstructure of the microcrystalline glass. 2The content of is 3.00 mol% to 5.00 mol%, preferably 3.00 mol% to 4.50 mol%, and more preferably 3.00 mol% to 4.00 mol%.
[0118] In some embodiments, ZrO 2 The content of can be 3.00mol%, 3.25mol%, 3.50mol%, 3.75mol%, 4.00mol%, 4.25mol%, 4.50mol%, 4.75mol%, 5.00mol% or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the spinel glass-ceramics with the desired properties of the present invention can be obtained.
[0119] The inventors have found that in the formula system of the present invention, Na 2 The proper increase of O content is not only conducive to reducing the melting temperature of the substrate glass, but also conducive to reducing the temperature of crystal precipitation during the preparation of spinel glass-ceramics, that is, reducing the heat treatment temperature. More importantly, it helps to ensure that the spinel glass-ceramics obtains higher stress performance during the chemical strengthening process. 2 When the O content is too high, it will cause phase separation in the base glass during the melting and annealing process, and will provide a large amount of free oxygen, which will have an adverse effect on the glass network structure. 2 The content of O is 7.20 mol% to 14.00 mol%, preferably 7.20 mol% to 13.00 mol%, and more preferably 7.20 mol% to 12.50 mol%.
[0120] In some embodiments, Na 2 The content of O can be 7.20mol%, 8.00mol%, 9.00mol%, 10.00mol%, 11.00mol%, 12.00mol%, 12.50mol%, 13.00mol%, 14.00mol%, or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the spinel glass-ceramics with the desired properties of the present invention can be obtained.
[0121] The inventors have found that in the formulation system of the present invention, K 2 O is an optional component that helps improve the low temperature melting property and formability of the base glass. + Radius larger than Na + , add appropriate amount of K 2O can reduce the crystallization tendency of the base glass and increase the transparency and gloss of the base glass. 2 O, not only easily leads to the reduction of chemical stability and hardness of spinel glass-ceramics, but also easily leads to the breakage of the obtained spinel glass-ceramics. Therefore, in the present invention, K 2 The content of O is 0.00 mol% to 2.00 mol%, preferably 0.00 mol% to 1.00 mol%.
[0122] In some embodiments, K 2 The content of O can be 0.00mol%, 0.25mol%, 0.50mol%, 0.75mol%, 1.00mol%, 1.25mol%, 1.50mol%, 1.75mol%, 2.00mol%, or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the spinel glass-ceramics with the desired properties of the present invention can be obtained.
[0123] The inventors have found that in the formula system of the present invention, an appropriate amount of B 2 O 3 It can not only greatly reduce the difficulty of melting the substrate glass, but also help promote the precipitation of the main crystal phase spinel. 2 O 3 When the addition amount is too low, it is easy to cause melting defects in the preparation of the substrate glass. 2 O 3 When the amount added is too high, the ion exchange capacity of the spinel glass-ceramics will be inhibited. 2 O 3 The content of is 3.00 mol% to 8.00 mol%, preferably 3.00 mol% to 7.50 mol%.
[0124] In some embodiments, B 2 O 3 The content of can be 3.00mol%, 3.50mol%, 4.00mol%, 4.50mol%, 5.00mol%, 5.50mol%, 6.00mol%, 6.50mol%, 7.00mol%, 7.50mol%, 8.00mol% or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the spinel glass-ceramics with the desired properties of the present invention can be obtained.
[0125] The inventors have found that in the formulation system of the present invention, Y 2O 3 It is an optional component that improves the hardness and chemical stability of spinel glass-ceramics and helps to inhibit crystallization during the molding of the substrate glass. 2 O 3 It can improve the density of the glass phase, thereby improving the intrinsic strength and overall strength of the spinel glass-ceramics. 2 O 3 Can be used with ZrO 2 The formation of eutectic is beneficial to reduce ZrO 2 The unevenness caused by precipitation. 2 O 3 When the content is too high, it will not only affect the precipitation of spinel crystals, but also reduce the ion exchange performance / chemical strengthening performance of spinel glass-ceramics. 2 O 3 The content is 0.00mol%~1.00mol%.
[0126] In some embodiments, Y 2 O 3 The content of can be 0.00mol%, 0.10mol%, 0.20mol%, 0.30mol%, 0.40mol%, 0.50mol%, 0.60mol%, 0.70mol%, 0.80mol%, 0.90mol%, 1.00mol% or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the spinel glass-ceramics with the desired properties of the present invention can be obtained.
[0127] The inventors have found that in the formulation system of the present invention, although BaO can improve the melting effect of the substrate glass, it will also inhibit the growth of grains to a certain extent and has a strong inhibitory effect on Na-K exchange. Therefore, in the present invention, the content of BaO is 0.00mol% to 2.10mol%, preferably 0.00mol% to 1.80mol%, and more preferably 0.00mol% to 1.50mol%.
[0128] In some embodiments, the content of BaO can be 0.00mol%, 0.10mol%, 0.20mol%, 0.30mol%, 0.40mol%, 0.50mol%, 0.60mol%, 0.70mol%, 0.80mol%, 0.90mol%, 1.00mol%, 1.20mol%, 1.50mol%, 1.80mol%, 2.00mol%, 2.10mol%, or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the spinel glass-ceramics with the desired properties of the present invention can be obtained.
[0129] In some embodiments, BaO is preferably not included in the composition of the spinel glass-ceramic.
[0130] The inventors have found that by adjusting the amount of each oxide in the formula, the specific content of each oxide component can be coordinated to produce a spinel glass-ceramic with a specific composition and structure. The spinel glass-ceramic has a specific network structure, and a large number of main crystal phases (Zn, Mg)Al with high Young's modulus and shear modulus are evenly distributed in the specific network structure. 2 O 4 , while ensuring that the spinel glass-ceramics have high intrinsic strength, the ion exchange capacity of the spinel glass-ceramics is significantly improved, so that the spinel glass-ceramics can simultaneously obtain a higher compressive stress layer depth and excellent surface stress characteristics after chemical strengthening. The spinel glass-ceramics can be chemically strengthened through chemical strengthening treatment to obtain chemically strengthened glass-ceramics with both excellent surface stress characteristics and excellent deep stress characteristics. The high intrinsic strength combined with the excellent surface stress characteristics and the excellent deep stress characteristics endow the chemically strengthened glass-ceramics with excellent mechanical strength, especially with excellent drop impact resistance.
[0131] In some embodiments of the present invention, the composition of each component of the spinel glass-ceramics satisfies the following conditions, based on the molar percentage of each oxide in the spinel glass-ceramics composition:
[0132] The value of X is calculated based on the following formula (1), 30.00%≤X≤50.00%,
[0133] X = 2.1 × (Al 2 O 3 -MgO-ZnO) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O+K 2 O+B 2 O3 )×100% Formula (1);
[0134] and / or,
[0135] The value of Y is calculated based on the following formula (2): 60.00%≤Y≤80.00%,
[0136] Y=(2.7×Na 2 O+1.8×(Al 2 O 3 -MgO-ZnO)) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O+K 2 O+B 2 O 3 )×100% Formula (2).
[0137] The inventors have found that by controlling the X value calculated based on the above formula (1) within a suitable range through the specific proportional relationship of the above-mentioned oxide components, it can be further ensured that the spinel glass-ceramics of the present invention obtains excellent deep stress properties after chemical strengthening, such as obtaining a high potassium-sodium exchange depth, that is, obtaining a high compressive stress layer depth.
[0138] The inventors have also found that by controlling the Y value calculated based on the above formula (2) within a suitable range through the specific ratio of the above oxide components, it can further ensure that the spinel glass-ceramics of the present invention obtains excellent surface stress characteristics after chemical strengthening, such as obtaining a high surface K 2 O concentration.
[0139] In some embodiments, the value of X may be 30.00%, 32.00%, 34.00%, 35.00%, 36.00%, 38.00%, 40.00%, 42.00%, 44.00%, 45.00%, 46.00%, 48.00%, 50.00%, or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the spinel glass-ceramics having the desired properties of the present invention can be obtained.
[0140] In some embodiments, the Y value may be 60.00%, 62.00%, 64.00%, 65.00%, 66.00%, 68.00%, 70.00%, 72.00%, 74.00%, 75.00%, 76.00%, 78.00%, 80.00% or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the spinel glass-ceramics having the desired properties of the present invention can be obtained.
[0141] In the present invention, each substance in the above equations (1) and (2) represents the molar percentage of the corresponding substance. For example, Na 2 O represents Na 2 The molar percentage of O, Al 2 O 3 Represents Al 2 O 3 Mole percentage content, etc.
[0142] In some embodiments, the spinel glass-ceramics that meets the above-mentioned oxide content range requirements and meets the X value and Y value requirements in the relationship (1) and (2) can be processed by chemical strengthening to obtain chemically strengthened glass-ceramics with excellent drop impact resistance.
[0143] In some embodiments of the present invention, the composition of the spinel glass-ceramics satisfies the following conditions based on the molar percentage of each oxide in the spinel glass-ceramics composition: A is calculated based on the following formula (3), A≤0.18, preferably A is 0.05 to 0.15, A=0.65×Al 2 O 3 +3.5×ZrO 2 -0.8×Na 2 O-2.5×B 2 O 3 Formula (3).
[0144] The inventors have also found that by controlling the A value calculated based on the following formula (3) within a suitable range through the specific ratio of the above oxide components, it is possible to further ensure that a transparent substrate glass that meets the requirements is obtained. In formula (3), each substance represents the molar percentage content data of the corresponding substance, and the unit is not involved in the calculation. For example, in spinel glass-ceramics, Al 2 O 3 The molar percentage of Na 2 The molar percentage of O is 10.00 mol%, then, in formula (3), Al 2 O 3 Take 0.25, Na 2For O, take 0.10, and so on for other oxides.
[0145] In some embodiments, the value of A can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.18, or a value within a numerical range consisting of any two of the above values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the spinel glass-ceramics with the desired properties of the present invention can be obtained.
[0146] In some embodiments of the present invention, the composition of the spinel glass-ceramics further includes: 0.00 mol% to 5.00 mol% of a colorant; expressed in terms of molar percentage of oxides, the colorant includes: 0.00 mol% to 4.00 mol% of NiO, 0.00 mol% to 5.00 mol% of Ni 2 O 3 0.00mol%~2.00mol%, Pr 2 O 5 0.00mol%~2.00mol%, CoO 0.00mol%~2.00mol%, Co 2 O 3 0.00mol%~1.00mol%,Cu 2 O 0.00mol%~2.20mol%, CeO 2 0.00mol%~2.00mol%,Fe 2 O 3 0.00mol%~3.50mol%, MnO 2 0.00mol%~4.00mol%, Er 2 O 3 0.00mol%~1.00mol%, Nd 2 O 3 0.00 mol% to 2.00 mol%. By adding a proper amount of colorant into the formula system of the present invention, the desired color of the spinel glass-ceramics can be adjusted according to actual conditions.
[0147] In some embodiments, the content of the colorant can be 0.00 mol%, 0.50 mol%, 1.00 mol%, 1.50 mol%, 2.00 mol%, 2.50 mol%, 3.00 mol%, 3.50 mol%, 4.00 mol%, 4.50 mol%, 5.00 mol% or a value within a numerical range consisting of any two of the above values as endpoints.
[0148] In some embodiments, the content of NiO can be 0.00 mol%, 0.50 mol%, 1.00 mol%, 1.50 mol%, 2.00 mol%, 2.50 mol%, 3.00 mol%, 3.50 mol%, 4.00 mol%, or a value within a numerical range consisting of any two of the above values as endpoints. 2 O 3 The content of Pr can be 0.00mol%, 0.25mol%, 0.50mol%, 0.75mol%, 1.00mol%, 1.25mol%, 1.50mol%, 1.75mol%, 2.00mol% or a value within a numerical range consisting of any two of the above values as endpoints. 2 O 5 The content of CoO may be 0.00 mol%, 0.25 mol%, 0.50 mol%, 0.75 mol%, 1.00 mol%, 1.25 mol%, 1.50 mol%, 1.75 mol%, 2.00 mol%, or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, the content of CoO may be 0.00 mol%, 0.25 mol%, 0.50 mol%, 0.75 mol%, 1.00 mol%, 1.25 mol%, 1.50 mol%, 1.75 mol%, 2.00 mol%, or a value within a numerical range consisting of any two of the above values as endpoints. 2 O 3 The content of Cu can be 0.00 mol%, 0.10 mol%, 0.20 mol%, 0.30 mol%, 0.40 mol%, 0.50 mol%, 0.60 mol%, 0.70 mol%, 0.80 mol%, 0.90 mol%, 1.00 mol% or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, Cu 2 The content of O can be 0.00 mol%, 0.25 mol%, 0.50 mol%, 0.75 mol%, 1.00 mol%, 1.25 mol%, 1.50 mol%, 1.75 mol%, 2.00 mol%, 2.20 mol% or a value within a numerical range consisting of any two of the above values as endpoints. 2The content of Fe may be 0.00 mol%, 0.25 mol%, 0.50 mol%, 0.75 mol%, 1.00 mol%, 1.25 mol%, 1.50 mol%, 1.75 mol%, 2.00 mol% or a value within a numerical range consisting of any two of the above values as endpoints. 2 O 3 The content of MnO can be 0.00 mol%, 0.50 mol%, 1.00 mol%, 1.50 mol%, 2.00 mol%, 2.50 mol%, 3.00 mol%, 3.50 mol% or a value within a numerical range consisting of any two of the above values as endpoints. 2 The content of Er can be 0.00 mol%, 0.50 mol%, 1.00 mol%, 1.50 mol%, 2.00 mol%, 2.50 mol%, 3.00 mol%, 3.50 mol%, 4.00 mol% or a value within a numerical range consisting of any two of the above values as endpoints. 2 O 3 The content of Nd can be 0.00 mol%, 0.10 mol%, 0.20 mol%, 0.30 mol%, 0.40 mol%, 0.50 mol%, 0.60 mol%, 0.70 mol%, 0.80 mol%, 0.90 mol%, 1.00 mol% or a value within a numerical range consisting of any two of the above values as endpoints. 2 O 3 The content can be 0.00 mol%, 0.25 mol%, 0.50 mol%, 0.75 mol%, 1.00 mol%, 1.25 mol%, 1.50 mol%, 1.75 mol%, 2.00 mol% or a value within a numerical range consisting of any two of the above values as endpoints.
[0149] It should be understood that in specific embodiments, any of the above ranges can be combined with any other ranges. When the colorant comprises two or more substances, the total content of the colorant should be less than or equal to 5.00 mol%.
[0150] NiO and Ni 2 O 3 It can be used to prepare brown or green substrate glass, glass-ceramics or glass products. 2 O 3 Can be used alone or in combination. 2 O 5 It can be used to prepare green substrate glass, glass-ceramics or glass products, usually used alone. CoO and Co2 O 3 Can be used to prepare blue substrate glass, glass-ceramic or glass products. CoO and Co 2 O 3 Can be used alone or in combination. 2 O can be used to prepare yellow substrate glass, glass-ceramics or glass products. 2 O can be used alone or in combination with CeO 2 Mixed use. CeO 2 Can be used to prepare yellow substrate glass, glass-ceramics or glass products. CeO 2 Can be used alone or with Cu 2 O mixed with Fe 2 O 3 It can be used to prepare black or smoke-gray substrate glass, glass-ceramics or glass products. 2 O 3 It can be used alone or mixed with CoO. 2 O 3 The two can be mixed, or they can be mixed with CoO and NiO. 2 O 3 , NiO three kinds of mixed use. Fe 2 O 3 With CoO or Co 2 O 3 Or NiO mixed use can deepen the coloring of the base glass, microcrystalline glass or glass products. 2 It can be used to prepare purple substrate glass, glass-ceramics or glass products, usually used alone. 2 O 3 It can be used to prepare pink substrate glass, glass-ceramics or glass products, usually used alone. 2 O 3 It can be used to prepare purple-red substrate glass, glass-ceramics or glass products. By adjusting the content of various colorants within the above range, the colorants can be fully melted in the substrate glass, glass-ceramics or glass products to obtain substrate glass, glass-ceramics or glass products of the desired color.
[0151] In some embodiments of the present invention, the composition of the spinel glass-ceramics preferably does not include TiO 2 The inventors of the present invention have found through extensive research that in the formulation system of the present invention, the use of TiO 2 When used as a nucleating agent, it will affect the color of the substrate glass and increase the heat treatment temperature of the substrate glass for preparing spinel glass-ceramics. 2After the heat treatment, the thermal expansion coefficient of the substrate glass will increase to a certain extent, which may easily lead to the breakage of the spinel glass-ceramics after heat treatment. Therefore, in some embodiments, the components of the spinel glass-ceramics provided by the present invention preferably do not include TiO 2 .
[0152] In some embodiments of the present invention, the spinel glass-ceramics further comprises a secondary crystalline phase, wherein the secondary crystalline phase comprises tetragonal ZrO 2 , baddeleyite, quartz, mullite and cordierite. In some embodiments, the main crystalline phase (Zn, Mg)Al 2 O 4 The spinel glass-ceramics of the above-mentioned secondary crystalline phase can be used to produce chemically strengthened glass-ceramics with excellent drop impact resistance.
[0153] In some embodiments of the present invention, the crystallinity of the spinel glass-ceramics is greater than or equal to 30wt%, preferably 30.00wt% to 50.00wt%, and more preferably 35.00wt% to 50.00wt%. High crystallinity means that in the spinel glass-ceramics, based on the mass of the spinel glass-ceramics, the content of the crystalline phase / crystalline phase accounts for a high proportion, which can give the spinel glass-ceramics a higher intrinsic strength, so that the spinel glass-ceramics and the spinel glass-ceramics products of the present invention have excellent mechanical properties. In some embodiments, the crystallinity can be 30.00wt%, 32.00wt%, 34.00wt%, 35.00wt%, 36.00wt%, 38.00wt%, 40.00wt%, 42.00wt%, 44.00wt%, 45.00wt%, 46.00wt%, 48.00wt%, 50.00wt%, 60.00wt%, 70.00wt% or a value within a numerical range consisting of any two of the above values as endpoints.
[0154] In some embodiments of the present invention, in the spinel glass-ceramics, the average grain size is 10.0 nm to 1000.0 nm, preferably 10.0 nm to 500.0 nm, and more preferably 10.0 nm to 100.0 nm. In some embodiments, in the spinel glass-ceramics, the average grain size can be 10.0nm, 20.0nm, 30.0nm, 40.0nm, 50.0nm, 60.0nm, 70.0nm, 80.0nm, 90.0nm, 100.0nm, 150.0nm, 200.0nm, 250.0nm, 300.0nm, 350.0nm, 400.0nm, 450.0nm, 500.0nm, 600.0nm, 700.0nm, 800.0nm, 900.0nm, 1000.0nm or a value within a numerical range formed by taking any two of the above values as endpoints.
[0155] In some embodiments of the present invention, the haze of 0.7 mm thick spinel glass-ceramics is 60.00% to 99.90%. In some embodiments, the haze of 0.7 mm thick spinel glass-ceramics can be 60.00%, 65.00%, 70.00%, 75.00%, 80.00%, 85.00%, 90.00%, 95.00%, 99.00%, 99.90% or a value within a numerical range consisting of any two of the above values as endpoints.
[0156] In some embodiments of the present invention, the spinel glass-ceramic comprises a color presented in CIE LAB color space coordinates, measured from the reflectance spectrum using a spectrophotometer with mirror reflection at an observation angle of 10° and CIE illuminant D65, and the L value, a value, and b value satisfy: the L value is 20.00 to 99.99; the a value is -5.00 to +25.00; and the b value is -50.00 to +5.00.
[0157] In some embodiments of the present invention, the Young's modulus of the spinel glass-ceramics is greater than or equal to 100 GPa, preferably 100 GPa to 140 GPa, and more preferably 110 GPa to 140 GPa. This indicates that the spinel glass-ceramics of the present invention have high intrinsic strength. It should be understood that the higher the intrinsic strength of the glass-ceramics, the stronger the ability of the glass-ceramics to resist external damage.
[0158] In some embodiments, the Young's modulus of the spinel glass-ceramics can be 100 GPa, 105 GPa, 110 GPa, 115 GPa, 120 GPa, 125 GPa, 130 GPa, 135 GPa, 140 GPa, or a value within a numerical range consisting of any two of the above values as endpoints. The spinel glass-ceramics has the above Young's modulus, which indicates that it has high intrinsic strength, thereby ensuring that it has excellent mechanical properties, which is conducive to obtaining chemically strengthened glass-ceramics with excellent drop impact resistance.
[0159] In the present invention, those skilled in the art can select the thickness of the spinel glass-ceramics according to the needs, and the present invention is not limited. Exemplarily, the thickness of the spinel glass-ceramics can be 0.2mm to 5.0mm, preferably 0.2mm to 2.0mm. Exemplarily, the thickness of the spinel glass-ceramics can be 0.2mm, 0.5mm, 0.7mm, 0.8mm, 0.9mm, 1.0mm, 1.2mm, 1.5mm, 1.6mm, 1.8mm, 2.0mm, 2.5mm, 2.8mm, 3.0mm, 3.5mm, 3.8mm, 4.0mm, 4.5mm, 4.8mm, 5.0mm or a value within the numerical range formed by any two of the above values as endpoints.
[0160] A second aspect of the present invention provides a method for preparing the spinel glass-ceramics in any of the aforementioned embodiments, comprising the following steps:
[0161] (1) Preparing substrate glass; the composition of the substrate glass, expressed in terms of molar percentage of oxides, includes: SiO 2 38.00mol%~48.30mol%, Al 2 O 3 25.50mol%~30.00mol%, MgO 5.00mol%~8.00mol%, ZnO 8.00mol%~14.00mol%, ZrO 2 3.00 mol%~5.00 mol%, Na 2 O 7.20mol%~14.00mol%, K 2 O 0.00mol%~2.00mol%, B 2 O 3 3.00 mol%~8.00 mol%, Y 2 O 3 0.00mol%~1.00mol%, BaO 0.00mol%~2.10mol%; the composition of the base glass does not include Li 2 O. The substrate glass can be prepared by a conventional preparation method known in the art, and the present invention is not limited thereto.
[0162] (2) Preparation of glass-ceramics: The substrate glass obtained in step (1) is heat-treated to obtain the spinel glass-ceramics in any of the aforementioned embodiments.
[0163] In some embodiments of the present invention, the heat treatment in step (2) includes a nucleation treatment and a crystallization treatment. Preferably, the temperature of the nucleation treatment is T 1 600℃~850℃, more preferably T 1 In some embodiments, the temperature of the nucleation treatment T 1 The nucleation treatment time t may be 600°C, 625°C, 650°C, 675°C, 700°C, 725°C, 750°C, 775°C, 800°C, 825°C, 850°C or a value within a range of values consisting of any two of the above values as endpoints. 1 0h~72h, more preferably t 1 0h~24h, more preferably t 1 In some embodiments, the nucleation treatment time t 1It can be 0h, 8h, 16h, 24h, 32h, 40h, 48h, 56h, 64h, 72h or a value within a range of values formed by taking any two of the above values as endpoints. Preferably, the temperature T of the crystallization treatment is 2 In some embodiments, the crystallization temperature T 2 The crystallization treatment time t can be 850°C, 875°C, 900°C, 925°C, 950°C, 975°C, 1000°C, 1025°C, 1050°C, 1075°C, 1100°C or a value within a numerical range consisting of any two of the above values as endpoints. 2 0.1h~72h, preferably t 2 0.1h~24h, more preferably t 2 In some embodiments, the crystallization treatment time t 2 It can be 0.1h, 8h, 16h, 24h, 32h, 40h, 48h, 56h, 64h, 72h or a value within a range of values formed by any two of the above values as endpoints. By adjusting the process parameters of the above nucleation treatment and crystallization treatment, a spinel glass-ceramic with a specific crystal phase composition and structure can be obtained, so that the obtained spinel glass-ceramic has high intrinsic strength and the required ion exchange capacity, thereby ensuring that the obtained spinel glass-ceramic can be prepared into a chemically strengthened glass-ceramic with excellent drop impact resistance by chemical strengthening.
[0164] It should be understood that when the substrate glass is heat treated, one-step heat treatment can be performed, or two-step or multi-step heat treatment can be performed. If a one-step heat treatment is performed, it means that the nucleation treatment is not performed separately, and the nucleation and target crystal growth are directly performed in a one-step heating process, which can be understood as directly performing a crystallization treatment. If a two-step heat treatment is performed, it means that a two-step heating process is performed, first a nucleation treatment, i.e., a nucleation treatment, is performed, and then a target crystal growth treatment, i.e., a crystallization treatment, is performed. If a multi-step heat treatment is performed, then the nucleation treatment stage and / or the crystallization treatment stage adopts a step-by-step heating method, that is, the entire heat treatment process will be heated multiple times (more than twice).
[0165] It should be understood that in the present invention, the nucleation treatment is to increase the temperature to a prescribed nucleation treatment temperature (also called nucleation temperature), and after reaching the nucleation treatment temperature, keep the temperature for a certain time, and the holding time here is the nucleation treatment time (also called nucleation time). The crystallization treatment is to increase the temperature to a prescribed crystallization treatment temperature (also called crystallization temperature), and after reaching the crystallization treatment temperature, keep the temperature for a certain time, and the holding time here is the crystallization treatment time (also called crystallization time).
[0166] In some embodiments of the present invention, in step (2), when heat treatment is performed, the heating rate is controlled to be 5K / min to 15K / min, preferably 5K / min to 10K / min. In some embodiments, the heating rate can be 5K / min, 6K / min, 7K / min, 8K / min, 9K / min, 10K / min, 11K / min, 12K / min, 13K / min, 14K / min, 15K / min or a value within a numerical range consisting of any two of the above values as endpoints. By adjusting the heating rate, it is beneficial to adjust the structure of the microcrystalline glass, thereby obtaining a spinel microcrystalline glass with a specific structure.
[0167] It should be understood that the composition of the substrate glass in the present invention is the same as the composition of the spinel glass-ceramics in the present invention, in terms of mol % of oxides.
[0168] In some embodiments of the present invention, the composition of the substrate glass satisfies, in terms of the molar percentage of each oxide in the substrate glass composition:
[0169] The value of X is calculated based on the following formula (1), 30.00%≤X≤50.00%,
[0170] X = 2.1 × (Al 2 O 3 -MgO-ZnO) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O+K 2 O+B 2 O 3 )×100% Formula (1);
[0171] and / or, the value of Y is calculated based on the following formula (2), 60.00%≤Y≤80.00%,
[0172] Y=(2.7×Na 2 O+1.8×(Al 2 O 3 -MgO-ZnO)) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O+K 2 O+B 2 O 3 )×100% Formula (2);
[0173] and / or, the value of A is calculated based on the following formula (3), A≤0.18, preferably the value of A is 0.05 to 0.15,
[0174] A=0.65×Al 2 O 3 +3.5×ZrO 2 -0.8×Na 2 O-2.5×B 2 O 3 Formula (3);
[0175] And / or, the composition of the substrate glass further includes: 0 mol% to 5.00 mol% of a colorant; expressed in terms of molar percentage of oxides, the colorant includes: NiO 0.00 mol% to 4.00 mol%, Ni 2 O 3 0.00mol%~2.00mol%, Pr 2 O 5 0.00mol%~2.00mol%, CoO 0.00mol%~2.00mol%, Co 2 O 3 0.00mol%~1.00mol%,Cu 2 O0.00mol%~2.20mol%, CeO 2 0.00mol%~2.00mol%,Fe 2 O 3 0.00mol%~3.50mol%, MnO 2 0.00mol%~4.00mol%, Er 2 O 3 0.00mol%~1.00mol%, Nd 2 O 3 0.00mol%~2.00mol%;
[0176] And / or, the composition of the substrate glass does not include TiO 2 ; and / or, the composition of the substrate glass does not include BaO.
[0177] The third aspect of the present invention provides a chemically strengthened glass-ceramic, wherein the chemically strengthened glass-ceramic is obtained by chemically strengthening the spinel glass-ceramic in any of the aforementioned embodiments, or by chemically strengthening the spinel glass-ceramic prepared by the preparation method in any of the aforementioned embodiments. The aforementioned spinel glass-ceramic of the present invention has a specific composition and structure, so that it has high intrinsic strength and excellent ion exchange capacity. The spinel glass-ceramic can be prepared into a chemically strengthened glass-ceramic with excellent surface stress characteristics and excellent deep stress characteristics by chemical strengthening, thereby ensuring that the obtained chemically strengthened glass-ceramic has excellent drop impact resistance.
[0178] For the chemically strengthened glass-ceramics of the present invention: a compressive stress layer with a certain depth will be formed on the surface of the spinel glass-ceramics through ion exchange, and at the same time, a tensile stress layer that can achieve force balance with the compressive stress layer will be formed inside the spinel glass-ceramics. It should be understood that after the chemical strengthening treatment, the composition at the surface of the glass-ceramics may be different from the composition of the newly formed glass-ceramics (i.e., glass-ceramics that have not undergone ion exchange). That is, in the chemically strengthened glass-ceramics prepared from the above-mentioned spinel glass-ceramics of the present invention, the composition of the compressive stress layer formed on the surface through ion exchange may be different from the composition of the spinel glass-ceramics. This is because during ion exchange, a type of alkali metal ion (for example, Li + Or Na + ) will be replaced by larger alkali metal ions (e.g., Na + or K + ) is replaced by, such as Na in glass-ceramics + With K in salt bath + Exchange, K + Replaced by, and / or, Li in glass-ceramics + With Na in salt bath + Exchange, by Na + However, in the embodiment, the composition of the glass-ceramic at the center of the depth of the glass product or near the center of the depth will still have the composition of the newly formed glass-ceramic. That is, in the chemically strengthened glass-ceramic made from the spinel glass-ceramic of the present invention, the composition of the tensile stress layer formed inside will still have the composition of the spinel glass-ceramic of the present invention.
[0179] In the present invention, since the chemical strengthening process is the exchange of alkali metal ions (such as lithium ions, sodium ions, potassium ions), the main crystal phase of the spinel glass-ceramics of the present invention is (Zn, Mg)Al 2 O 4 , the secondary crystalline phase includes tetragonal ZrO 2 , one or more of baddeleyite, quartz, mullite and cordierite. The crystal phase does not contain alkali metal and does not participate in ion exchange. Therefore, the composition of the main crystal phase and the secondary crystal phase in the spinel glass-ceramics does not change basically before and after strengthening.
[0180] In some embodiments of the present invention, the salt bath for chemical strengthening treatment is a molten salt containing potassium salt, and the potassium salt includes one or more of potassium nitrate, potassium sulfate, and potassium carbonate, preferably potassium nitrate. Preferably, the temperature of the salt bath for chemical strengthening treatment is T 3 380℃~600℃, preferably T 3 400°C to 550°C, preferably T 3In some embodiments, the temperature of the salt bath for chemical strengthening treatment is T 3 The temperature may be 380°C, 400°C, 425°C, 450°C, 475°C, 500°C, 525°C, 550°C, 575°C, 600°C, or a value within a range of any two of the above values. 3 1h~48h, preferably t 3 6h~24h, more preferably t 3 In some embodiments, the time of chemical strengthening treatment t 3 It can be 1h, 4h, 8h, 12h, 16h, 20h, 24h, 28h, 32h, 36h, 40h, 44h, 48h or a value within a range of values formed by any two of the above values as endpoints. By adopting the above chemical strengthening treatment process scheme to strengthen the spinel microcrystalline glass with a specific composition and structure, a chemically strengthened microcrystalline glass with excellent surface stress characteristics and excellent deep stress characteristics can be obtained, thereby ensuring that the obtained chemically strengthened microcrystalline glass has excellent drop impact resistance.
[0181] In some embodiments of the present invention, in the chemically strengthened glass-ceramics, along the thickness direction of the chemically strengthened glass-ceramics, the depth DOL_0 from any surface of the chemically strengthened glass-ceramics to a position close to the surface and having the same potassium concentration as that at the center of the chemically strengthened glass-ceramics is K ≥0.07t, preferably DOL_ K 0.07t~0.22t, more preferably DOL_ K 0.10t~0.22t, more preferably DOL_ K The term "any surface" herein refers to any main surface of the chemically strengthened microcrystalline glass sheet.
[0182] In some embodiments, the depth DOL_ K It can be 0.07t, 0.08t, 0.09t, 0.10t, 0.11t, 0.12t, 0.13t, 0.14t, 0.15t, 0.16t, 0.17t, 0.18t, 0.19t, 0.20t, 0.21t, 0.22t or a value within a range of values formed by any two of the above values as endpoints. Wherein, t is the thickness of the chemically strengthened microcrystalline glass. The chemically strengthened microcrystalline glass has the above depth DOL_ K, indicating that during the chemical strengthening process, the depth of K ions in the salt bath entering the spinel glass-ceramics is large, and the depth of the compressive stress layer formed by the K-Na exchange is deep, which is conducive to obtaining chemically strengthened glass-ceramics with excellent drop impact resistance. For example, when the thickness of the chemically strengthened glass-ceramics is 0.7 mm, the depth DOL_ K ≥49.00μm, preferably DOL_ K 49.00 μm to 154.00 μm, and DOL_ K 70 μm to 154 μm, and DOL_ K It is 90μm~154μm.
[0183] In some embodiments of the present invention, the surface K of the chemically strengthened glass-ceramics 2 O concentration C ≥ 9.00 wt%, preferably 9.00 wt% to 16.00 wt%. In some embodiments, the surface K of the chemically strengthened microcrystalline glass 2 The O concentration C can be 9.00wt%, 10.00wt%, 11.00wt%, 12.00wt%, 13.00wt%, 14.00wt%, 15.00wt%, 16.00wt% or a value within a numerical range consisting of any two of the above values as endpoints. 2 When the O concentration C is within the above range, it means that during the chemical strengthening treatment, the more potassium ions of the potassium salt in the salt bath are exchanged with the sodium ions on the surface of the spinel glass-ceramics, the greater the volume difference produced on the surface of the spinel glass-ceramics, and the higher the surface compressive stress that the spinel glass-ceramics can obtain, and the better the surface stress characteristics.
[0184] In some embodiments of the present invention, the chemically strengthened microcrystalline glass with a thickness of 0.7 mm is subjected to a drop resistance test using 120-mesh sandpaper, and the average anti-sandpaper drop height h of the chemically strengthened microcrystalline glass is greater than or equal to 1.80 m, preferably h is greater than or equal to 1.90 m, and more preferably h is greater than or equal to 2.00 m; the average anti-sandpaper drop height h is based on the test of at least 10 samples. In some embodiments, the chemically strengthened microcrystalline glass with a thickness of 0.7 mm is subjected to a drop resistance test using 120-mesh sandpaper, and the average anti-sandpaper drop height h of the chemically strengthened microcrystalline glass is 1.90 m to 2.50 m, preferably h is 2.00 m to 2.50 m. In some embodiments, the average anti-sandpaper drop height h can be 1.80 m, 1.90 m, 2.00 m, 2.10 m, 2.20 m, 2.30 m, 2.40 m, 2.50 m, or a value within a numerical range consisting of any two of the above values as endpoints. This indicates that the chemically strengthened glass-ceramics provided by the present invention has excellent drop impact resistance.
[0185] In some embodiments of the present invention, a 0.7 mm thick chemically strengthened glass-ceramics is subjected to a 2.50 m drop test using 120-mesh sandpaper, and the pass rate of the drop test of the chemically strengthened glass-ceramics is greater than or equal to 50%, preferably greater than or equal to 60%. More preferably, it is greater than or equal to 70%, and more preferably, the pass rate is 60% to 100%; the pass rate is based on the test of at least 10 samples. In some embodiments, the pass rate of the chemically strengthened glass-ceramics in a 2.5 m drop test (120-mesh sandpaper) can be 60%, 70%, 80%, 90% or 100%, or the pass rate of the 2.5 m drop test (120-mesh sandpaper) within the numerical range consisting of any two of the above specific values as endpoints.
[0186] The spinel glass-ceramics and chemically strengthened glass-ceramics with excellent performance provided by the present invention can be used in many aspects, such as work surfaces, other surfaces, covers of consumer electronic devices, appliance doors, floor tiles, wall panels, storage containers, etc. Other surfaces may include but are not limited to exterior wall surfaces, stair tread surfaces, column veneers, counter surfaces, etc. The types of consumer electronic devices may include but are not limited to handheld, desktop mounted, and wall mounted, etc. The covers may include but are not limited to mobile phone back panels, tablet computer back panels, etc., and the storage containers may include but are not limited to plates, beverage bottles, etc.
[0187] The fourth aspect of the present invention provides a glass device, which is made of the spinel glass-ceramic in any of the aforementioned embodiments, or made of the chemically strengthened glass-ceramic in any of the aforementioned embodiments. For example, the glass device may include but is not limited to the back panel of a mobile phone, an external device of an electronic product, etc. The spinel glass-ceramic and chemically strengthened glass-ceramic provided by the present invention have excellent mechanical properties, and the chemically strengthened glass-ceramic has excellent drop impact resistance, so the glass device provided by the present invention also has excellent mechanical properties.
[0188] The fifth aspect of the present invention provides an electronic device, which includes the spinel microcrystalline glass in any of the foregoing embodiments, or includes the chemically strengthened microcrystalline glass in any of the foregoing embodiments. For example, the electronic device may include but is not limited to mobile phones, tablet computers, smart wearables, displays or televisions, etc. Smart wearables may include but are not limited to electronic watches, smart bracelets, smart watches, smart glasses, etc., and displays may include but are not limited to high-definition displays, car displays, aircraft displays, etc. Exemplarily, the electronic device may include a housing and an electronic component partially located in the housing, the housing includes a front surface, a rear surface and a side surface, the electronic component includes a display device, the display device is located at the front surface of the housing or adjacent to the front surface, and the chemically strengthened glass provided by the present invention can be applied to the rear surface and / or side surface of the housing.
[0189] A sixth aspect of the present invention provides a substrate glass, which can be used to prepare the spinel glass-ceramics in any of the above embodiments; the composition of the substrate glass, expressed in molar percentage of oxides, includes: SiO 2 38.00mol%~48.30mol%, Al 2 O 3 25.50mol%~30.00mol%, MgO 5.00mol%~8.00mol%, ZnO 8.00mol%~14.00mol%, ZrO 2 3.00 mol%~5.00 mol%, Na 2 O 7.20mol%~14.00mol%, K 2 O 0.00mol%~2.00mol%, B 2 O 3 3.00 mol%~8.00 mol%, Y 2 O 3 0.00mol%~1.00mol%, BaO 0.00mol%~2.10mol%; the composition of the base glass does not include Li 2 O.
[0190] In some embodiments of the present invention, the composition of the substrate glass satisfies, in terms of the molar percentage of each oxide in the substrate glass composition:
[0191] The value of X is calculated based on the following formula (1), 30.00%≤X≤50.00%,
[0192] X = 2.1 × (Al 2 O 3 -MgO-ZnO) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2 O+K 2 O+B 2 O 3 )×100% Formula (1);
[0193] and / or, the value of Y is calculated based on the following formula (2), 60.00%≤Y≤80.00%,
[0194] Y=(2.7×Na 2 O+1.8×(Al 2 O 3 -MgO-ZnO)) / (SiO 2 +Al 2 O 3 -MgO-ZnO+Na 2O+K 2 O+B 2 O 3 )×100% Formula (2);
[0195] and / or, the value of A is calculated based on the following formula (3), A≤0.18, preferably the value of A is 0.05 to 0.15,
[0196] A=0.65×Al 2 O 3 +3.5×ZrO 2 -0.8×Na 2 O-2.5×B 2 O 3 Formula (3).
[0197] In some embodiments of the present invention, the composition of the substrate glass further includes: 0 mol% to 5.00 mol% of a colorant; expressed in terms of molar percentage of oxides, the colorant includes: NiO 0.00 mol% to 4.00 mol%, Ni 2 O 3 0.00mol%~2.00mol%, Pr 2 O 5 0.00mol%~2.00mol%, CoO 0.00mol%~2.00mol%, Co 2 O 3 0.00mol%~1.00mol%,Cu 2 O 0.00mol%~2.20mol%, CeO 2 0.00mol%~2.00mol%,Fe 2 O 3 0.00mol%~3.50mol%, MnO 2 0.00mol%~4.00mol%, Er 2 O 3 0.00mol%~1.00mol%, Nd 2 O 3 0.00mol%~2.00mol%.
[0198] In some embodiments of the present invention, the composition of the substrate glass does not include TiO 2 ; and / or, the composition of the substrate glass does not include BaO.
[0199] In the present invention, the preparation method of the substrate glass can adopt conventional preparation methods known in the art, and the present invention is not limited to this. In some embodiments of the present invention, the preparation method of the substrate glass includes but is not limited to float, overflow, rolling or casting processes.
[0200] In some embodiments of the present invention, when preparing the substrate glass, a clarifier may be added to the raw materials for preparing the substrate glass, and the clarifier includes but is not limited to NaCl, Na 2 SO 4 SnO 2 , As 2 O 3 , Sb 2 O 3 , NaNO 3 , KNO 3 , CeO 2 and (NH 4 ) 2 SO 4 Based on the total mass of the raw materials of the substrate glass, the amount of the clarifier added is 0.01wt% to 2.00wt%, preferably 0.01wt% to 1.50wt%. For example, the amount of the clarifier added can be 0.01wt%, 0.20wt%, 0.40wt%, 0.80wt%, 1.00wt%, 1.20wt%, 1.40wt%, 1.60wt%, 1.80wt%, 2.00wt% or a value within a numerical range consisting of any two of the above values as endpoints.
[0201] In some embodiments of the present invention, the preparation process of the substrate glass is as follows: after mixing the raw materials according to the formula, a clarifier is added, and the glass is melted at 1480°C to 1650°C for 3h to 24h, preferably for 3h to 6h. After the melting treatment is completed, the glass liquid is cast into a mold for forming, and after cooling to 850°C to 1000°C, it is preferably placed in an annealing furnace for annealing at a temperature of 500°C to 650°C. The annealing is kept for 12h to 72h, and then cooled to room temperature with the furnace to obtain the substrate glass.
[0202] In some embodiments, the melting temperature of the substrate glass may be 1480°C, 1500°C, 1520°C, 1540°C, 1560°C, 1580°C, 1600°C, 1620°C, 1650°C, or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, the melting time of the substrate glass may be 3h, 3.5h, 4.0h, 4.5h, 5.0h, 5.5h, 6.0h, 8.0h, 10.0h, 12.0h, 14.0h, 16.0h, 18.0h, 20.0h, 22.0h, 24.0h, or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, after the substrate glass is formed, it can be cooled to 850°C, 875°C, 900°C, 925°C, 950°C, 975°C, 1000°C, or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, the annealing temperature of the substrate glass can be 500°C, 525°C, 550°C, 575°C, 600°C, 625°C, 650°C, or a value within a numerical range consisting of any two of the above values as endpoints. In some embodiments, the holding time during annealing of the substrate glass can be 12h, 22h, 32h, 42h, 52h, 62h, 72h, or a value within a numerical range consisting of any two of the above values as endpoints.
[0203] Test method:
[0204] 1. Differential Scanning Calorimetry (DSC) Test
[0205] After the substrate glass is crushed, ground and sieved through 200 meshes to obtain a sample, 10 mg of the sample is weighed and heated from room temperature to 1100°C at a heating rate of 10°C / min under a nitrogen atmosphere using a differential thermal analyzer to obtain a DSC test curve of the sample. The differential thermal analyzer used in the present invention is a Mettler-Toledo TGA / DSC3+ thermogravimetric and synchronous thermal analyzer, and the standard used in the test is α-Al 2 O 3 The powder and sample container are platinum crucibles, the instrument is placed at an ambient temperature of 24°C and an air humidity of 40%.
[0206] 2. X-ray diffraction (XRD) test
[0207] The microcrystalline glass was crushed and ground into samples with a particle size of less than 75 μm. The ground samples were tested using an X-ray diffractometer to obtain XRD diffraction peak curves and XRD diffraction data. The XRD diffraction data were then analyzed using Jade software to obtain the crystalline phase of the sample. The X-ray diffractometer was Shimadzu XRD-6100, the incident angle range used in the test was 2θ=10°~80°, the scanning speed was 6° / min, the operating voltage was 40 kV, and the operating current was 30 mA.
[0208] Average grain size: The average grain size of the sample can be calculated using the result data obtained from the XRD test according to the Scherrer formula D = Kλ / (βcosθ). Among them, λ is the X-ray wavelength, λ = 0.154056nm, β is the half-height width of the diffraction peak, K = 0.89, and θ is the Bragg diffraction angle. Specifically, the RAW file (diffraction spectrum) output by the XRD instrument is curve-fitted in the Jade software, and Jade outputs a fitting report. According to the angle 2θ value and PeakFWHM value (half-height width of the diffraction peak) corresponding to each diffraction peak in the fitting report, and the Peak FWHM value is converted into radians: β = (FWHM / 180×3.14), the grain size of each diffraction peak is calculated by the Scherrer formula D = Kλ / (βcosθ) and then averaged to obtain the average grain size.
[0209] Crystallinity: It can also be called crystal content. The XRD test results (RAW format) are imported into the X-ray diffraction data Rietveld refinement software Jade for fitting and calculation to obtain the crystallinity of the microcrystalline glass sample. Specifically, the ratio of the fitted crystal phase peak area to the fitted total peak area is the crystallinity of the microcrystalline glass.
[0210] 3. Thickness test
[0211] The thickness of glass-ceramics is tested using a micrometer.
[0212] It should be understood that when chemical strengthening is performed, the degree of ion exchange changes gradually from the surface to the center in the thickness direction of the glass-ceramics, and the total Na-K and / or Li-Na exchange amount generally does not exceed 1% of the total mass of the sample, and the difference in ion radius is at the pm (picometer) level, so the expansion effect in the thickness direction is extremely slight, and it can be approximately considered that the thickness has basically not changed. That is, the thickness of the glass-ceramics changes very little before and after chemical strengthening.
[0213] 4. Optical performance test
[0214] With reference to the national standard GB / T 7962.12-2010 Test method for colorless optical glass Part 12: Spectral transmittance, a haze meter was used to test the average transmittance, haze, L value, a value and b value of the microcrystalline glass.
[0215] Specifically, in the same embodiment or the same comparative example, 5 glass-ceramic samples of the same specification are selected for testing, and the haze, L value, a value and b value of the glass-ceramic samples to be tested, as well as the average transmittance of the glass-ceramic samples to be tested under wavelength light in the range of 360nm to 740nm, are tested using a haze meter. The characteristic results of each parameter measured by the 5 glass-ceramic samples are averaged and used as the characteristic results of each parameter of the glass-ceramic samples of the embodiment or comparative example.
[0216] The haze meter used in the test of the present invention is a Japanese Konica Minolta spectrophotometer CM-3600A. When testing transmittance and haze, the transmission mode of the haze meter is used; when testing L value, a value, and b value, the reflection mode of the haze meter is used. The wavelength range of the transmittance test is 360nm to 740nm, the wavelength interval is 10nm, the illumination light source is a pulse xenon lamp X4, the ambient temperature of the instrument is 24°C, and the air humidity is 40%.
[0217] 5. Calculation of exchange volume
[0218] The ratio of the mass difference of the spinel glass-ceramics before and after chemical strengthening treatment to the mass of the spinel glass-ceramics before chemical strengthening treatment.
[0219] 6. Surface K 2 O concentration C test
[0220] In the present invention, the surface K of the chemically strengthened microcrystalline glass 2 The O concentration was measured by X-ray fluorescence spectrometer (XRF). The equipment model used was (Thermo Scientific ARL PERFORM'X), the target material was Rh (rhodium), the light tube voltage was 40kW, the current was 60mA, the collimator was 0.15, the crystal was LiF200, the detector was FPC, the test range was 29mm circle, and the analysis software was UniQuant standardless analysis.
[0221] Surface K 2 O concentration C = K 2 O mass / total mass of oxides, where oxides include SiO 2 、Al 2 O 3 、ZrO 2 、Na 2 O.K 2 XRF can accurately test the oxides such as O, excluding B 2 O 3XRF cannot accurately test the content of the oxides obtained. XRF testing uses a non-standard test and does not test the concentration of elements or their oxides with atomic numbers 6 and below in chemically strengthened microcrystalline glass. That is, the K obtained by XRF testing 2 When calculating the O concentration, the total mass of oxides does not include the mass of elements with atomic numbers 6 and below or their oxides in the glass.
[0222] 7. Drop test
[0223] 7.1 Average sandpaper drop resistance test
[0224] The average anti-sandpaper drop height refers to the sum of the measured anti-sandpaper drop heights of multiple glass-ceramics samples in the same embodiment or the same comparative example, and the ratio of the number of glass-ceramics samples to the sum of the measured anti-sandpaper drop heights of each sample, which can be used to characterize the anti-drop performance of the glass-ceramics. Ten identical glass-ceramics samples were taken from each batch for testing, and the average anti-sandpaper drop height was:
[0225]
[0226] Wherein, n is the number of glass-ceramic samples tested in each batch, and hi is the sandpaper drop resistance height of a single sample tested.
[0227] Among them, the test method for the sandpaper drop height of a single sample is:
[0228] Step 1: Paste 120-grit sandpaper on the lower surface of the 160g model machine, and place the model machine on the green figure LT-SKDL-CD drop machine;
[0229] Step 2: Place a glass-ceramic sample to be tested with a length, width and thickness of 50mm×50mm×0.7mm directly under the model machine, with the glass-ceramic sample facing the sandpaper. Make the model machine fall from a certain drop height to impact the glass-ceramic sample directly under the model machine. If the glass-ceramic sample does not break, the drop height of the model machine is increased according to a certain rule. For example, the drop height starts from 0.4m, and the sample is dropped once. If it does not break, increase the height by 0.1m each time and drop again until the glass sample breaks;
[0230] Step 3: The last drop height of the glass-ceramic sample when it was broken is recorded as the anti-sandpaper drop height. For example, if the drop height when it was broken is 0.5m, then the anti-sandpaper drop height of the sample is 0.4m.
[0231] 7.2 2.5m drop test pass rate
[0232] The pass rate of the 2.5m drop test refers to the ratio of the number of samples that passed the drop test to the number of samples that were tested after multiple glass-ceramics samples in the same embodiment or the same comparative example were dropped from a height of 2.5m. After the drop test, if the glass-ceramics sample does not break, it is recorded as passed, otherwise it is recorded as failed; it can be used to characterize the drop resistance of glass-ceramics. Take 10 identical glass-ceramics samples from each batch for testing.
[0233]
[0234] Wherein, n is the number of glass-ceramic samples that pass the test in each batch, N is the number of glass-ceramic samples that pass the test in each batch, and P is the pass rate of the drop test.
[0235] Among them, the method for a single sample to undergo a 2.5m drop test is as follows:
[0236] Step 1: Paste 120-grit sandpaper on the lower surface of the 160g model machine, and place the model machine on the green figure LT-SKDL-CD drop machine;
[0237] Step 2: Place a glass-ceramic sample to be tested with a length, width and thickness of 50mm×50mm×0.7mm directly under the model machine, with the glass-ceramic sample facing the sandpaper. Make the model machine fall once from a drop height of 2.5m to impact the glass-ceramic sample directly under the model machine. If the glass-ceramic sample does not break, it is recorded as passed, otherwise it is recorded as failed.
[0238] 8. Electron probe X-ray microanalysis (EPMA) test
[0239] The chemically strengthened glass-ceramic sample was carbon-sprayed, and the focused electron beam was slowly scanned along a straight line selected in the thickness direction of the sample to obtain the element composition of the test area and the element concentration distribution on the sample surface.
[0240] The electron probe X-ray microanalyzer used in the present invention is Shimadzu's EPMA-1720, which performs line analysis and tests the following elements: Li, Na, K, Mg, Zn, Zr, Al, and Si.
[0241] 9. Young’s modulus test
[0242] The Young's modulus of the obtained microcrystalline glass sample is tested by ultrasonic wave. The testing instrument used in the present invention is UMS-100 ultrasonic material characterization system.
[0243] 10. Density test
[0244] The present invention uses an electronic density balance SD-200L produced by Japan ALFA MIRAGE to test the density of microcrystalline glass, and the testing principle is the "Archimedes drainage method".
[0245] In the above test method, after the microcrystalline glass bricks in the embodiments and comparative examples are shaped, cut and polished, microcrystalline glass samples (microcrystalline glass polished sheets) of the desired size can be obtained, and then tested, such as microcrystalline glass polished sheets with a length, width and thickness of 50mm×50mm×0.7mm.
[0246] Example 1
[0247] <Preparation of substrate glass>
[0248] According to the formula S1 in Table 1, the raw material formula for spinel microcrystalline glass production was converted and the ingredients were prepared. The total mass of the raw materials was 1000 g, and then mixed with a V-type mixer for 30 minutes. After mixing, 5 g of clarifier NaCl was added, and then transferred to a platinum crucible and melted in a 1650°C lifting furnace (lifting furnace model: SJF1750, manufacturer: Nanjing Boyuntong Instrument Technology Co., Ltd.) for 5 hours, and then poured into a stainless steel mold preheated at 300°C for molding and cooling. It was cooled to 900°C and then placed in a 600°C annealing furnace for annealing for 24 hours. It was then cooled to room temperature with the furnace to obtain the substrate glass.
[0249] like Figure 1 As shown, in the DSC test spectrum of the substrate glass prepared above, the temperature of the first endothermic peak is 735°C, and the temperature of the first exothermic peak is 848°C.
[0250] <Preparation of spinel glass-ceramics>
[0251] The substrate glass prepared as above was heat-treated in a resistance furnace (equipment model: SLX1400-40, manufacturer: Shanghai Shengli Testing Instrument Co., Ltd.) to obtain a spinel glass-ceramic brick.
[0252] Specifically, a one-step heat treatment process is used, that is, the temperature is directly raised to the crystallization temperature for crystallization. The crystallization temperature T 2 The temperature is 1100℃, and the crystallization time is t 2 The heating rate during the heat treatment process is controlled to be 10K / min. That is, the resistance furnace is heated from room temperature to 1100°C at a heating rate of 10K / min and kept at this temperature for 4 hours.
[0253] The spinel glass-ceramic sample brick is cut, CNC processed and polished to obtain a mirror-smooth spinel glass-ceramic polished sheet. In the present invention, the processed spinel glass-ceramic polished sheet has a length, width and thickness of 50 mm×50 mm×0.7 mm.
[0254] Embodiment 2 to Embodiment 4, Embodiment 6 to Embodiment 7, Embodiment 10 to Embodiment 17
[0255] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 1. The corresponding formula in Table 2 is shown in Table 1.
[0256] Example 5
[0257] In <Preparation of substrate glass>, replace formula S1 with formula S3. The corresponding formula S3 is shown in Table 1.
[0258] <Preparation of spinel glass-ceramics>
[0259] The substrate glass prepared as above was heat-treated in a resistance furnace (equipment model: SLX1400-40, manufacturer: Shanghai Shengli Testing Instrument Co., Ltd.) to obtain a spinel glass-ceramic brick.
[0260] Specifically, the two-step heat treatment process is adopted, firstly the temperature is raised to the nucleation temperature for nucleation treatment, and then the temperature is raised to the crystallization temperature for crystallization treatment; the heating rate during the nucleation treatment and crystallization process is 10K / min. Among them, the nucleation temperature T 1 The temperature is 800℃, and the nucleation time is t 1 The crystallization temperature is 4h; 2 The temperature is 1000℃, and the crystallization time is t 2 The rest is the same as in Example 1.
[0261] Embodiment 8-embodiment 9
[0262] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 5. The corresponding formula in Table 2 is shown in Table 1.
[0263] Embodiment 18
[0264] <Preparation of Chemically Strengthened Glass-Ceramics>
[0265] The spinel glass-ceramic in Example 1 (i.e., a spinel glass-ceramic polished sheet of 50 mm×50 mm×0.7 mm) was placed at T 3 100wt% KNO at 450℃ 3 Treatment in salt bath 3 For 24 hours, chemically strengthened microcrystalline glass is obtained.
[0266] Example 19 to Example 31
[0267] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 18.
[0268] Comparative Examples 1 to 4, Comparative Examples 6 to 7
[0269] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 1.
[0270] Comparative Example 5
[0271] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as Example 5.
[0272] Comparative Example 8 to Comparative Example 13
[0273] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 18.
[0274] The formulations of the embodiments and comparative examples are shown in Table 1, and the preparation parameters and performance tests of the embodiments and comparative examples are shown in Table 2 and Table 3.
[0275]
[0276]
[0277]
[0278]
[0279] Refer to Table 1, Table 2 and Table 3: The formulas and average transmittances of spinel glass-ceramics of Examples 1 to 17 are within the scope of the present invention. The main crystalline phases of the spinel glass-ceramics in the above examples are (Zn, Mg)Al 2 O 4 .
[0280] Specifically, Figures 2 to 4 As shown, they are the XRD spectra of the spinel glass-ceramics in Example 1, Example 6 and Example 7, respectively. It can be seen from the figures that zinc-aluminum spinel and magnesium-aluminum spinel exist in them. Figure 6 Graphs showing the transmittance of the spinel glass-ceramics in Examples 1, 2 and 7 in the visible light band, all of which have transmittances less than 70% in the visible light band.
[0281] It can be seen from Examples 1 to 17 that when the spinel glass-ceramics prepared by the formula provided by the present invention have a crystallinity and haze (C) within the range of the present invention, have a suitable density, and have the color and texture of jade (such as Figure 5b shown).
[0282] The spinel glass-ceramics obtained in the embodiment of the present invention not only has a high Young's modulus, but also can be obtained by chemical strengthening treatment to have a high depth DOL_ K and high surface K 2O concentration C of chemically strengthened microcrystalline glass, thereby ensuring that the prepared chemically strengthened microcrystalline glass has excellent drop impact resistance. Specifically, the average anti-sandpaper drop height h of the 0.7 mm thick chemically strengthened microcrystalline glass obtained in Examples 18 to 31 of the present invention is 2.06 to 2.45 m, and the pass rate of the 2.5 m drop test is 100%.
[0283] Specifically, Figure 7 and Figure 8 As shown, there are relationship diagrams between the K and Na element contents and the depth below the surface in the chemically strengthened microcrystalline glass in Example 21 and Example 24, respectively. It can be seen from the figure that the potassium content in the surface area is relatively high.
[0284] In Examples 14 to 17, colorants were added to the formulas of S11 to S14, and the obtained spinel glass-ceramics were blue, purple, pink, and light purple, respectively. That is, by adding different colorants to the formula, spinel glass-ceramics of different colors can be obtained. This shows that the color of the spinel glass-ceramics can be adjusted by adjusting the type of colorant in the formula.
[0285] The formulas of the spinel glass-ceramics in Comparative Examples 1 to 7 are not within the scope of the present invention. In particular, the substrate glass in Comparative Example 4 was directly cracked during the heat treatment process for preparing the glass-ceramics (e.g. Figure 5a As shown), the desired spinel glass-ceramics cannot be obtained. Although comparative examples 1 to 3 and comparative examples 5 to 7 can produce spinel glass-ceramics, the spinel glass-ceramics obtained therefrom cannot obtain high depth DOL_ after chemical strengthening treatment. K and high surface K 2 The chemically strengthened glass-ceramics with a concentration of 0.0 C are also limited in the drop impact resistance of the chemically strengthened glass-ceramics obtained therefrom. Specifically, the average sandpaper drop resistance height h of the 0.7 mm thick chemically strengthened glass-ceramics obtained in Comparative Examples 8 to 13 is 1.05 to 1.75 m, all lower than 1.80 m, and the pass rate of the 2.5 m drop test is less than 50%.
[0286] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0287] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0288] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.
Claims
1. A spinel glass-ceramic, characterized in that: The spinel glass-ceramics includes a main crystalline phase (Zn, Mg)Al2O4; the average transmittance of the spinel glass-ceramics with a thickness of 0.7 mm in the visible light range is less than or equal to 70.00%; Expressed in terms of molar percentage of oxides, the composition of the spinel glass-ceramics includes: SiO2 38.00mol% to 48.30mol%, Al2O3 25.50mol% to 30.00mol%, MgO 5.00mol% to 8.00mol%, ZnO 8.00mol% to 14.00mol%, ZrO2 3.00mol% to 5.00mol%, Na2O 7.20mol% to 14.00mol%, K2O 0.00mol% to 2.00mol%, B2O3 3.00mol% to 8.00mol%, Y2O3 0.00mol% to 1.00mol%, BaO 0.00mol% to 2.10mol%; the composition of the spinel glass-ceramics does not include Li2O; and Wherein, the composition of the spinel glass-ceramics satisfies, in terms of the molar percentage of each oxide in the composition of the spinel glass-ceramics: The value of X is calculated based on the following formula (1), 30.00%≤X≤50.00%, X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3)×100% Formula (1); and, The value of Y is calculated based on the following formula (2): 60.00%≤Y≤80.00%, Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3)×100% Formula (2).
2. The spinel glass-ceramic according to claim 1, wherein: Calculated by the molar percentage of each oxide in the spinel glass-ceramics composition, the composition of the spinel glass-ceramics satisfies: The value of A is calculated based on the following formula (3), A≤0.18, A = 0.65×Al2O3+3.5×ZrO2-0.8×Na2O-2.5×B2O3 formula (3).
3. The spinel glass-ceramic according to claim 2, wherein: The A value is 0.05~0.
15.
4. The spinel glass-ceramic according to any one of claims 1 to 3, wherein: The spinel glass-ceramics also comprises 0 mol% to 5.00 mol% of a colorant; Expressed in molar percentage of oxides, the colorant includes: NiO 0.00mol%~4.00mol%, Ni2O3 0.00mol%~2.00mol%, Pr2O5 0.00mol%~2.00mol%, CoO 0.00mol%~2.00mol%, Co2O3 0.00mol%~1.00mol%, Cu2O 0.00mol%~2.20mol%, CeO2 0.00mol%~2.00mol%, Fe2O3 0.00mol%~3.50mol%, MnO2 0.00mol%~4.00mol%, Er2O3 0.00mol%~1.00mol%, and Nd2O3 0.00mol%~2.00mol%.
5. The spinel glass-ceramic according to any one of claims 1 to 3, wherein: The spinel glass-ceramics does not include TiO2 in its composition; and / or, the spinel glass-ceramics does not include BaO in its composition.
6. The spinel glass-ceramic according to any one of claims 1 to 3, wherein: The spinel glass-ceramics also include a secondary crystalline phase, and the secondary crystalline phase includes one or more of tetragonal ZrO2, baddeleyite, quartz, mullite and cordierite.
7. The spinel glass-ceramic according to claim 4, wherein: The spinel glass-ceramics also include a secondary crystalline phase, and the secondary crystalline phase includes one or more of tetragonal ZrO2, baddeleyite, quartz, mullite and cordierite.
8. The spinel glass-ceramic according to claim 5, wherein: The spinel glass-ceramics also include a secondary crystalline phase, and the secondary crystalline phase includes one or more of tetragonal ZrO2, baddeleyite, quartz, mullite and cordierite.
9. The spinel glass-ceramic according to any one of claims 1 to 3, wherein: The spinel glass-ceramics has a crystallinity greater than or equal to 30.00 wt %; and / or, the spinel glass-ceramics has an average grain size of 10.0 nm to 1000.0 nm.
10. The spinel glass-ceramic according to claim 9, wherein: The spinel glass-ceramics has a crystallinity of 30.00 wt% to 50.00 wt%; and / or, the spinel glass-ceramics has an average grain size of 10.0 nm to 500.0 nm.
11. The spinel glass-ceramic according to claim 9, wherein: The spinel glass-ceramics has a crystallinity of 35.00 wt% to 50.00 wt%; and / or, the spinel glass-ceramics has an average grain size of 10.0 nm to 100.0 nm.
12. The spinel glass-ceramic according to claim 4, wherein: The spinel glass-ceramics has a crystallinity greater than or equal to 30.00 wt %; and / or, the spinel glass-ceramics has an average grain size of 10.0 nm to 1000.0 nm.
13. The spinel glass-ceramic according to claim 5, wherein: The spinel glass-ceramics has a crystallinity greater than or equal to 30.00 wt %; and / or, the spinel glass-ceramics has an average grain size of 10.0 nm to 1000.0 nm.
14. The spinel glass-ceramic according to claim 6, wherein: The spinel glass-ceramics has a crystallinity greater than or equal to 30.00 wt %; and / or, the spinel glass-ceramics has an average grain size of 10.0 nm to 1000.0 nm.
15. The spinel glass-ceramic according to any one of claims 1 to 3, wherein: The haze of the 0.7 mm thick spinel glass-ceramics is 60.00% to 99.90%.
16. The spinel glass-ceramic according to claim 4, wherein: The haze of the 0.7 mm thick spinel glass-ceramics is 60.00% to 99.90%.
17. The spinel glass-ceramic according to claim 5, wherein: The haze of the 0.7 mm thick spinel glass-ceramics is 60.00% to 99.90%.
18. The spinel glass-ceramic according to claim 6, wherein: The haze of the 0.7 mm thick spinel glass-ceramics is 60.00% to 99.90%.
19. The spinel glass-ceramic according to claim 9, wherein: The haze of the 0.7 mm thick spinel glass-ceramics is 60.00% to 99.90%.
20. The spinel glass-ceramic according to any one of claims 1 to 3, wherein: The spinel glass-ceramic includes a color presented in CIE LAB color space coordinates, and is measured from a reflectance spectrum using a spectrophotometer with mirror reflection at an observation angle of 10° and CIE illuminant D65, and the L value, a value, and b value satisfy: the L value is 20.00 to 99.99; the a value is -5.00 to +25.00; and the b value is -50.00 to +5.
00.
21. The spinel glass-ceramic according to claim 4, wherein: The spinel glass-ceramic includes a color presented in CIE LAB color space coordinates, and is measured from a reflectance spectrum using a spectrophotometer with mirror reflection at an observation angle of 10° and CIE illuminant D65, and the L value, a value, and b value satisfy: the L value is 20.00 to 99.99; the a value is -5.00 to +25.00; and the b value is -50.00 to +5.
00.
22. The spinel glass-ceramic according to claim 5, wherein: The spinel glass-ceramic includes a color presented in CIE LAB color space coordinates, and is measured from a reflectance spectrum using a spectrophotometer with mirror reflection at an observation angle of 10° and CIE illuminant D65, and the L value, a value, and b value satisfy: the L value is 20.00 to 99.99; the a value is -5.00 to +25.00; and the b value is -50.00 to +5.
00.
23. The spinel glass-ceramic according to claim 6, wherein: The spinel glass-ceramic includes a color presented in CIE LAB color space coordinates, and is measured from a reflectance spectrum using a spectrophotometer with mirror reflection at an observation angle of 10° and CIE illuminant D65, and the L value, a value, and b value satisfy: the L value is 20.00 to 99.99; the a value is -5.00 to +25.00; and the b value is -50.00 to +5.
00.
24. The spinel glass-ceramic according to claim 9, wherein: The spinel glass-ceramic includes a color presented in CIE LAB color space coordinates, and is measured from a reflectance spectrum using a spectrophotometer with mirror reflection at an observation angle of 10° and CIE illuminant D65, and the L value, a value, and b value satisfy: the L value is 20.00 to 99.99; the a value is -5.00 to +25.00; and the b value is -50.00 to +5.
00.
25. The spinel glass-ceramic according to claim 15, wherein: The spinel glass-ceramic includes a color presented in CIELAB color space coordinates, and is measured from a reflectance spectrum using a spectrophotometer with mirror reflection at an observation angle of 10° and CIE illuminant D65, and the L value, a value, and b value satisfy: the L value is 20.00 to 99.99; the a value is -5.00 to +25.00; and the b value is -50.00 to +5.
00.
26. The spinel glass-ceramic according to any one of claims 1 to 3, wherein: The Young's modulus of the spinel glass-ceramics is greater than or equal to 100 GPa.
27. The spinel glass-ceramic according to claim 26, wherein: The Young's modulus of the spinel glass-ceramics is 100 GPa to 140 GPa.
28. The spinel glass-ceramic according to claim 26, wherein: The Young's modulus of the spinel glass-ceramics is 110 GPa to 140 GPa.
29. The spinel glass-ceramic according to claim 4, wherein: The Young's modulus of the spinel glass-ceramics is greater than or equal to 100 GPa.
30. The spinel glass-ceramic according to claim 5, wherein: The Young's modulus of the spinel glass-ceramics is greater than or equal to 100 GPa.
31. The spinel glass-ceramic according to claim 6, wherein: The Young's modulus of the spinel glass-ceramics is greater than or equal to 100 GPa.
32. The spinel glass-ceramic according to claim 9, wherein: The Young's modulus of the spinel glass-ceramics is greater than or equal to 100 GPa.
33. The spinel glass-ceramic according to claim 15, wherein: The Young's modulus of the spinel glass-ceramics is greater than or equal to 100 GPa.
34. The spinel glass-ceramic according to claim 20, wherein: The Young's modulus of the spinel glass-ceramics is greater than or equal to 100 GPa.
35. The spinel glass-ceramic according to any one of claims 1 to 3, wherein: In the spinel glass-ceramics, The molar percentage of SiO2 is 38.00mol% to 48.00mol%; and / or, The molar percentage of MgO is 5.00 mol% to 7.00 mol%; and / or, The molar percentage of ZnO is 8.00 mol% to 13.00 mol%; and / or, The molar percentage of ZrO2 is 3.00mol% to 4.50mol%; and / or, The molar percentage of Na2O is 7.20mol% to 13.00mol%; and / or, The molar percentage of K2O is 0.00mol% to 1.00mol%; and / or, The molar percentage of B2O3 is 3.00mol% to 7.50mol%; and / or, The molar percentage of BaO is 0.00 mol% to 1.80 mol%.
36. The spinel glass-ceramic according to claim 35, wherein: In the spinel glass-ceramics, The molar percentage of SiO2 is 38.00mol% to 45.00mol%; and / or, The molar percentage of MgO is 5.00mol% to 6.50mol%; and / or, The molar percentage of ZnO is 8.50 mol% to 11.00 mol%; and / or, The molar percentage of ZrO2 is 3.00mol% to 4.00mol%; and / or, The molar percentage of Na2O is 7.20mol% to 12.50mol%; and / or, The molar percentage of BaO is 0.00 mol% to 1.50 mol%.
37. The spinel glass-ceramic according to claim 4, wherein: In the spinel glass-ceramics, The molar percentage of SiO2 is 38.00mol% to 48.00mol%; and / or, The molar percentage of MgO is 5.00 mol% to 7.00 mol%; and / or, The molar percentage of ZnO is 8.00 mol% to 13.00 mol%; and / or, The molar percentage of ZrO2 is 3.00mol% to 4.50mol%; and / or, The molar percentage of Na2O is 7.20mol% to 13.00mol%; and / or, The molar percentage of K2O is 0.00mol% to 1.00mol%; and / or, The molar percentage of B2O3 is 3.00mol% to 7.50mol%; and / or, the molar percentage of BaO is 0.00mol% to 1.80mol%.
38. The spinel glass-ceramic according to claim 5, wherein: In the spinel glass-ceramics, the molar percentage of SiO2 is 38.00 mol% to 48.00 mol%; and / or, The molar percentage of MgO is 5.00 mol% to 7.00 mol%; and / or, The molar percentage of ZnO is 8.00 mol% to 13.00 mol%; and / or, The molar percentage of ZrO2 is 3.00mol% to 4.50mol%; and / or, The molar percentage of Na2O is 7.20mol% to 13.00mol%; and / or, The molar percentage of K2O is 0.00mol% to 1.00mol%; and / or, The molar percentage of B2O3 is 3.00mol% to 7.50mol%; and / or, The molar percentage of BaO is 0.00 mol% to 1.80 mol%.
39. The spinel glass-ceramic according to claim 6, wherein: In the spinel glass-ceramics, the molar percentage of SiO2 is 38.00 mol% to 48.00 mol%; and / or, The molar percentage of MgO is 5.00 mol% to 7.00 mol%; and / or, The molar percentage of ZnO is 8.00 mol% to 13.00 mol%; and / or, The molar percentage of ZrO2 is 3.00mol% to 4.50mol%; and / or, The molar percentage of Na2O is 7.20mol% to 13.00mol%; and / or, The molar percentage of K2O is 0.00mol% to 1.00mol%; and / or, The molar percentage of B2O3 is 3.00mol% to 7.50mol%; and / or, The molar percentage of BaO is 0.00 mol% to 1.80 mol%.
40. The spinel glass-ceramic according to claim 9, wherein: In the spinel glass-ceramics, the molar percentage of SiO2 is 38.00 mol% to 48.00 mol%; and / or, The molar percentage of MgO is 5.00 mol% to 7.00 mol%; and / or, The molar percentage of ZnO is 8.00 mol% to 13.00 mol%; and / or, The molar percentage of ZrO2 is 3.00mol% to 4.50mol%; and / or, The molar percentage of Na2O is 7.20mol% to 13.00mol%; and / or, The molar percentage of K2O is 0.00mol% to 1.00mol%; and / or, The molar percentage of B2O3 is 3.00mol% to 7.50mol%; and / or, The molar percentage of BaO is 0.00 mol% to 1.80 mol%.
41. The spinel glass-ceramic according to claim 15, wherein: In the spinel glass-ceramics, the molar percentage of SiO2 is 38.00 mol% to 48.00 mol%; and / or, The molar percentage of MgO is 5.00 mol% to 7.00 mol%; and / or, The molar percentage of ZnO is 8.00 mol% to 13.00 mol%; and / or, The molar percentage of ZrO2 is 3.00mol% to 4.50mol%; and / or, The molar percentage of Na2O is 7.20mol% to 13.00mol%; and / or, The molar percentage of K2O is 0.00mol% to 1.00mol%; and / or, The molar percentage of B2O3 is 3.00mol% to 7.50mol%; and / or, The molar percentage of BaO is 0.00 mol% to 1.80 mol%.
42. The spinel glass-ceramic according to claim 20, wherein: In the spinel glass-ceramics, the molar percentage of SiO2 is 38.00 mol% to 48.00 mol%; and / or, The molar percentage of MgO is 5.00 mol% to 7.00 mol%; and / or, The molar percentage of ZnO is 8.00 mol% to 13.00 mol%; and / or, The molar percentage of ZrO2 is 3.00mol% to 4.50mol%; and / or, The molar percentage of Na2O is 7.20mol% to 13.00mol%; and / or, The molar percentage of K2O is 0.00mol% to 1.00mol%; and / or, The molar percentage of B2O3 is 3.00mol% to 7.50mol%; and / or, The molar percentage of BaO is 0.00 mol% to 1.80 mol%.
43. The spinel glass-ceramic according to claim 26, wherein: In the spinel glass-ceramics, the molar percentage of SiO2 is 38.00 mol% to 48.00 mol%; and / or, The molar percentage of MgO is 5.00 mol% to 7.00 mol%; and / or, The molar percentage of ZnO is 8.00 mol% to 13.00 mol%; and / or, The molar percentage of ZrO2 is 3.00mol% to 4.50mol%; and / or, The molar percentage of Na2O is 7.20mol% to 13.00mol%; and / or, The molar percentage of K2O is 0.00mol% to 1.00mol%; and / or, The molar percentage of B2O3 is 3.00mol% to 7.50mol%; and / or, The molar percentage of BaO is 0.00 mol% to 1.80 mol%.
44. A method for preparing the spinel glass-ceramics according to any one of claims 1 to 43, characterized in that: The steps include: (1) preparing a substrate glass; the composition of the substrate glass, expressed in terms of molar percentage of oxides, includes: SiO2 38.00mol% to 48.30mol%, Al2O3 25.50mol% to 30.00mol%, MgO 5.00mol% to 8.00mol%, ZnO 8.00mol% to 14.00mol%, ZrO2 3.00mol% to 5.00mol%, Na2O 7.20mol% to 14.00mol%, K2O 0.00mol% to 2.00mol%, B2O3 3.00mol% to 8.00mol%, Y2O3 0.00mol% to 1.00mol%, BaO 0.00mol% to 2.10mol%; the composition of the substrate glass does not include Li2O; (2) Preparation of glass-ceramics: heat-treating the substrate glass obtained in step (1) to obtain the spinel glass-ceramics according to any one of claims 1 to 43; Wherein, the composition of the substrate glass satisfies, based on the molar percentage of each oxide in the substrate glass composition: The value of X is calculated based on the following formula (1), 30.00%≤X≤50.00%, X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3)×100% Formula (1); and, The value of Y is calculated based on the following formula (2): 60.00%≤Y≤80.00%, Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3)×100% Formula (2).
45. The method for preparing spinel glass-ceramics according to claim 44, wherein: In step (2), the heat treatment includes nucleation treatment and crystallization treatment; wherein: The temperature of the nucleation treatment is 600°C to 850°C; the nucleation treatment time is 0h to 72h; the temperature of the crystallization treatment is 850°C to 1100°C, and the crystallization treatment time is 0.1h to 72h; and / or, In step (2), when performing heat treatment, the heating rate is controlled to be 5K / min to 15K / min.
46. The method for preparing spinel glass-ceramics according to claim 45, wherein: The temperature of the nucleation treatment is 650°C to 850°C; the nucleation treatment time is 0h to 24h; the temperature of the crystallization treatment is 850°C to 1100°C, and the crystallization treatment time is 0.1h to 24h; and / or, In step (2), when performing heat treatment, the heating rate is controlled to be 5K / min to 10K / min.
47. The method for preparing spinel glass-ceramics according to claim 46, wherein: The nucleation treatment time is 0h to 8h; the crystallization treatment temperature is 850°C to 1100°C, and the crystallization treatment time is 4h to 8h.
48. A method for preparing spinel glass-ceramics according to any one of claims 44 to 47, wherein: Calculated by the molar percentage of each oxide in the composition of the substrate glass, the composition of the substrate glass satisfies: The value of A is calculated based on the following formula (3), A≤0.18, A=0.65×Al2O3+3.5×ZrO2-0.8×Na2O-2.5×B2O3 Formula (3); and / or, The composition of the substrate glass also includes 0mol% to 5.00mol% of colorant; expressed in terms of molar percentage of oxides, the colorant includes: NiO 0.00mol% to 4.00mol%, Ni2O3 0.00mol% to 2.00mol%, Pr2O5 0.00mol% to 2.00mol%, CoO 0.00mol% to 2.00mol%, Co2O3 0.00mol% to 1.00mol%, Cu2O 0.00mol% to 2.20mol%, CeO2 0.00mol% to 2.00mol%, Fe2O3 0.00mol% to 3.50mol%, MnO2 0.00mol% to 4.00mol%, Er2O3 0.00mol% to 1.00mol%, Nd2O3 0.00mol% to 2.00mol%; and / or, The composition of the substrate glass does not include TiO2; and / or the composition of the substrate glass does not include BaO.
49. The method for preparing spinel glass-ceramics according to claim 48, wherein: The A value is 0.05~0.
15.
50. A chemically strengthened glass-ceramic, characterized in that: The chemically strengthened glass-ceramics is obtained by subjecting the spinel glass-ceramics described in any one of claims 1 to 43 to chemical strengthening treatment, or by subjecting the spinel glass-ceramics prepared by the preparation method described in any one of claims 44 to 49 to chemical strengthening treatment.
51. The chemically strengthened glass-ceramics according to claim 50, wherein: The salt bath for the chemical strengthening treatment is a molten salt containing potassium salt, and the potassium salt includes one or more of potassium nitrate, potassium sulfate, and potassium carbonate; the temperature of the salt bath for the chemical strengthening treatment is 380° C. to 600° C.; and the time for the chemical strengthening treatment is 1 hour to 48 hours.
52. The chemically strengthened glass-ceramics according to claim 51, wherein: The potassium salt is potassium nitrate; the temperature of the salt bath for the chemical strengthening treatment is 400° C. to 550° C.; and the time for the chemical strengthening treatment is 6 h to 24 h.
53. The chemically strengthened glass-ceramics according to claim 51, wherein: The temperature of the salt bath for the chemical strengthening treatment is 400° C. to 500° C.; the time for the chemical strengthening treatment is 12 h to 24 h.
54. The chemically strengthened glass-ceramics according to any one of claims 50 to 53, wherein: In the chemically strengthened glass-ceramics, along the thickness direction of the chemically strengthened glass-ceramics, the depth from any surface of the chemically strengthened glass-ceramics to a position close to the surface having the same potassium concentration as that at the center of the chemically strengthened glass-ceramics is ≥0.07t, where t is the thickness of the chemically strengthened glass-ceramics.
55. The chemically strengthened glass-ceramics according to claim 54, wherein: In the chemically strengthened glass-ceramics, along the thickness direction of the chemically strengthened glass-ceramics, the depth from any surface of the chemically strengthened glass-ceramics to a position close to the surface having the same potassium concentration as the center of the chemically strengthened glass-ceramics is 0.07t to 0.22t, where t is the thickness of the chemically strengthened glass-ceramics.
56. The chemically strengthened glass-ceramics according to claim 54, wherein: In the chemically strengthened glass-ceramics, along the thickness direction of the chemically strengthened glass-ceramics, the depth from any surface of the chemically strengthened glass-ceramics to a position close to the surface having the same potassium concentration as the center of the chemically strengthened glass-ceramics is 0.10t to 0.22t, where t is the thickness of the chemically strengthened glass-ceramics.
57. The chemically strengthened glass-ceramics according to claim 54, wherein: In the chemically strengthened glass-ceramics, along the thickness direction of the chemically strengthened glass-ceramics, the depth from any surface of the chemically strengthened glass-ceramics to a position close to the surface having the same potassium concentration as the center of the chemically strengthened glass-ceramics is 0.13t to 0.22t, where t is the thickness of the chemically strengthened glass-ceramics.
58. The chemically strengthened glass-ceramics according to any one of claims 50 to 53, wherein: The surface K2O concentration of the chemically strengthened glass-ceramics is ≥9.00wt%.
59. The chemically strengthened glass-ceramics according to claim 58, wherein: The surface K2O concentration of the chemically strengthened glass-ceramics is 9.00wt% to 16.00wt%.
60. The chemically strengthened glass-ceramics according to claim 54, wherein: The surface K2O concentration of the chemically strengthened glass-ceramics is ≥9.00wt%.
61. The chemically strengthened glass-ceramics according to any one of claims 50 to 53, wherein: A 0.7 mm thick chemically strengthened glass-ceramics was subjected to a drop resistance test using 120-grit sandpaper. The average sandpaper resistance drop height of the chemically strengthened glass-ceramics was greater than or equal to 1.80 m.
62. The chemically strengthened glass-ceramics according to claim 61, wherein: A 0.7 mm thick chemically strengthened glass-ceramics was subjected to a drop resistance test using 120-grit sandpaper. The average sandpaper resistance drop height of the chemically strengthened glass-ceramics was greater than or equal to 1.90 m.
63. The chemically strengthened glass-ceramics according to claim 61, wherein: A 0.7 mm thick chemically strengthened glass-ceramics is subjected to a drop resistance test using 120-grit sandpaper. The average sandpaper resistance drop height of the chemically strengthened glass-ceramics is greater than or equal to 2.00 m.
64. The chemically strengthened glass-ceramics according to claim 54, wherein: A 0.7 mm thick chemically strengthened glass-ceramics was subjected to a drop resistance test using 120-grit sandpaper. The average sandpaper resistance drop height of the chemically strengthened glass-ceramics was greater than or equal to 1.80 m.
65. The chemically strengthened glass-ceramics according to claim 58, wherein: A 0.7 mm thick chemically strengthened glass-ceramics was subjected to a drop resistance test using 120-grit sandpaper. The average sandpaper resistance drop height of the chemically strengthened glass-ceramics was greater than or equal to 1.80 m.
66. The chemically strengthened glass-ceramics according to any one of claims 50 to 53, wherein: A 0.7 mm thick chemically strengthened glass-ceramics is subjected to a 2.5 m drop test using 120-mesh sandpaper, and the drop test pass rate of the chemically strengthened glass-ceramics is greater than or equal to 50%.
67. The chemically strengthened glass-ceramics according to claim 66, wherein: A 0.7 mm thick chemically strengthened glass-ceramics is subjected to a 2.5 m drop test using 120-mesh sandpaper, and the drop test pass rate of the chemically strengthened glass-ceramics is greater than or equal to 60%.
68. The chemically strengthened glass-ceramics according to claim 54, wherein: A 0.7 mm thick chemically strengthened glass-ceramics is subjected to a 2.5 m drop test using 120-mesh sandpaper, and the drop test pass rate of the chemically strengthened glass-ceramics is greater than or equal to 50%.
69. The chemically strengthened glass-ceramics according to claim 58, wherein: A 0.7 mm thick chemically strengthened glass-ceramics is subjected to a 2.5 m drop test using 120-mesh sandpaper, and the drop test pass rate of the chemically strengthened glass-ceramics is greater than or equal to 50%.
70. The chemically strengthened glass-ceramics according to claim 61, wherein: A 0.7 mm thick chemically strengthened glass-ceramics is subjected to a 2.5 m drop test using 120-mesh sandpaper, and the drop test pass rate of the chemically strengthened glass-ceramics is greater than or equal to 50%.
71. A chemically strengthened glass-ceramic, characterized in that: The chemically strengthened microcrystalline glass comprises a main crystalline phase (Zn, Mg) Al2O4; the surface of the chemically strengthened microcrystalline glass has a compressive stress layer, and the interior has a tensile stress layer, and the composition of the tensile stress layer in the chemically strengthened microcrystalline glass comprises: SiO2 38.00mol% to 48.30mol%, Al2O3 25.50mol% to 30.00mol%, MgO 5.00mol% to 8.00mol%, ZnO 8.00mol% to 14.00mol%, ZrO2 3.00mol% to 5.00mol%, Na2O 7.20mol% to 14.00mol%, K2O 0.00mol% to 2.00mol%, B2O3 3.00mol% to 8.00mol%, Y2O3 0.00mol%~1.00mol%, BaO0.00mol%~2.10mol%; the composition of the tensile stress layer does not include Li2O; and Wherein, in terms of the molar percentage of each oxide in the composition of the tensile stress layer in the chemically strengthened glass-ceramics, the composition of the tensile stress layer in the chemically strengthened glass-ceramics satisfies: The value of X is calculated based on the following formula (1), 30.00%≤X≤50.00%, X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3)×100% Formula (1); and, The value of Y is calculated based on the following formula (2): 60.00%≤Y≤80.00%, Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3)×100% Formula (2).
72. The chemically strengthened glass-ceramics according to claim 71, wherein: In terms of the molar percentage of each oxide in the composition of the tensile stress layer in the chemically strengthened glass-ceramics, the composition of the tensile stress layer in the chemically strengthened glass-ceramics satisfies: The value of A is calculated based on the following formula (3), A≤0.18, A = 0.65×Al2O3+3.5×ZrO2-0.8×Na2O-2.5×B2O3 formula (3).
73. The chemically strengthened glass-ceramics according to claim 72, wherein: The A value is 0.05~0.
15.
74. The chemically strengthened glass-ceramics according to any one of claims 71 to 73, wherein: In the chemically strengthened glass-ceramics, the composition of the tensile stress layer further includes 0 mol% to 5.00 mol% of a colorant; Expressed in molar percentage of oxides, the colorant includes: NiO 0.00mol%~4.00mol%, Ni2O3 0.00mol%~2.00mol%, Pr2O5 0.00mol%~2.00mol%, CoO 0.00mol%~2.00mol%, Co2O3 0.00mol%~1.00mol%, Cu2O 0.00mol%~2.20mol%, CeO2 0.00mol%~2.00mol%, Fe2O3 0.00mol%~3.50mol%, MnO2 0.00mol%~4.00mol%, Er2O3 0.00mol%~1.00mol%, and Nd2O3 0.00mol%~2.00mol%.
75. The chemically strengthened glass-ceramics according to any one of claims 71 to 73, wherein: The chemically strengthened glass-ceramics is chemically strengthened by a salt bath containing a molten salt of potassium salt; and / or, in the chemically strengthened glass-ceramics, the tensile stress layer does not include TiO2; And / or, in the chemically strengthened glass-ceramics, the composition of the tensile stress layer does not include BaO.
76. The chemically strengthened glass-ceramics according to any one of claims 71 to 73, wherein: The chemically strengthened glass-ceramics also include a secondary crystalline phase, which includes one or more of tetragonal ZrO2, baddeleyite, quartz, mullite and cordierite; and / or, in the chemically strengthened glass-ceramics, the degree of crystallinity is greater than or equal to 30.00wt%; and / or, in the chemically strengthened glass-ceramics, the average grain size is 10.0nm to 1000.0nm.
77. The chemically strengthened glass-ceramics according to any one of claims 71 to 73, wherein: The chemically strengthened glass-ceramics tensile stress layer is composed of: The molar percentage of SiO2 is 38.00mol% to 48.00mol%; and / or, The molar percentage of MgO is 5.00 mol% to 7.00 mol%; and / or, The molar percentage of ZnO is 8.00 mol% to 13.00 mol%; and / or, The molar percentage of ZrO2 is 3.00mol% to 4.50mol%; and / or, The molar percentage of Na2O is 7.20mol% to 13.00mol%; and / or, The molar percentage of K2O is 0.00mol% to 1.00mol%; and / or, The molar percentage of B2O3 is 3.00mol% to 7.50mol%; and / or, The molar percentage of BaO is 0.00 mol% to 1.80 mol%.
78. The chemically strengthened glass-ceramics according to any one of claims 71 to 73, wherein: In the chemically strengthened glass-ceramics, along the thickness direction of the chemically strengthened glass-ceramics, the depth from any surface of the chemically strengthened glass-ceramics to a position close to the surface having the same potassium concentration as that at the center of the chemically strengthened glass-ceramics is ≥0.07t, where t is the thickness of the chemically strengthened glass-ceramics.
79. The chemically strengthened glass-ceramics according to any one of claims 71 to 73, wherein: The surface K2O concentration of the chemically strengthened glass-ceramics is ≥9.00wt%.
80. The chemically strengthened glass-ceramics according to claim 78, wherein: The surface K2O concentration of the chemically strengthened glass-ceramics is ≥9.00wt%.
81. The chemically strengthened glass-ceramics according to claim 80, wherein: In the chemically strengthened glass-ceramics, along the thickness direction of the chemically strengthened glass-ceramics, the depth from any surface of the chemically strengthened glass-ceramics to a position close to the surface having the same potassium concentration as that at the center of the chemically strengthened glass-ceramics is 0.10t to 0.22t, where t is the thickness of the chemically strengthened glass-ceramics; and / or, the surface K2O concentration of the chemically strengthened glass-ceramics is 9.00wt% to 16.00wt%.
82. The chemically strengthened glass-ceramics according to any one of claims 71 to 73, wherein: A 0.7 mm thick chemically strengthened glass-ceramic is subjected to a drop test using 120-mesh sandpaper, and the average sandpaper drop resistance height of the chemically strengthened glass-ceramic is greater than or equal to 1.80 m; and / or a 0.7 mm thick chemically strengthened glass-ceramic is subjected to a 2.5 m drop test using 120-mesh sandpaper, and the drop test pass rate of the chemically strengthened glass-ceramic is greater than or equal to 50%.
83. A glass device, which is made of the spinel microcrystalline glass described in any one of Claims 1 to 43, or made of the chemically strengthened microcrystalline glass described in any one of Claims 50 to 70, or made of the chemically strengthened microcrystalline glass described in any one of Claims 71 to 82.
84. An electronic device comprising the spinel glass-ceramic described in any one of Claims 1-43, or the chemically strengthened glass-ceramic described in any one of Claims 50-70, or the chemically strengthened glass-ceramic described in any one of Claims 71-82.
85. A substrate glass, characterized in that The substrate glass can be used to prepare the spinel glass-ceramics according to any one of claims 1 to 43; the composition of the substrate glass, expressed in terms of molar percentage of oxides, includes: SiO2 38.00mol% to 48.30mol%, Al2O3 25.50mol% to 30.00mol%, MgO 5.00mol% to 8.00mol%, ZnO 8.00mol% to 14.00mol%, ZrO2 3.00mol% to 5.00mol%, Na2O 7.20mol% to 14.00mol%, K2O 0.00mol% to 2.00mol%, B2O3 3.00mol% to 8.00mol%, Y2O3 0.00mol% to 1.00mol%, BaO 0.00mol% to 2.10mol%; the composition of the substrate glass does not include Li2O; Wherein, the composition of the substrate glass satisfies, based on the molar percentage of each oxide in the substrate glass composition: The value of X is calculated based on the following formula (1), 30.00%≤X≤50.00%, X=2.1×(Al2O3-MgO-ZnO) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3)×100% Formula (1); and, The value of Y is calculated based on the following formula (2): 60.00%≤Y≤80.00%, Y=(2.7×Na2O+1.8×(Al2O3-MgO-ZnO)) / (SiO2+Al2O3-MgO-ZnO+Na2O+K2O+B2O3)×100% Formula (2).
86. The substrate glass according to claim 85, wherein: Calculated by the molar percentage of each oxide in the composition of the substrate glass, the composition of the substrate glass satisfies: The value of A is calculated based on the following formula (3), A≤0.18, A=0.65×Al2O3+3.5×ZrO2-0.8×Na2O-2.5×B2O3 Formula (3); and / or, The composition of the substrate glass further includes: 0 mol% to 5.00 mol% of colorant; expressed in terms of molar percentage of oxides, the colorant includes: NiO 0.00 mol% to 4.00 mol%, Ni2O3 0.00 mol% to 2.00 mol%, Pr2O5 0.00 mol% to 2.00 mol%, CoO 0.00 mol% to 2.00 mol%, Co2O3 0.00 mol% to 1.00 mol%, Cu2O 0.00 mol% to 2.20 mol%, CeO2 0.00 mol% to 2.00 mol%, Fe2O3 0.00 mol% to 3.50 mol%, MnO2 0.00 mol% to 4.00 mol%, Er2O3 0.00 mol% to 1.00 mol%, Nd2O3 0.00 mol% to 2.00 mol%; and / or, The composition of the substrate glass does not include TiO2; and / or the composition of the substrate glass does not include BaO.
87. The substrate glass according to claim 86, wherein: The A value is 0.05~0.15.
Citation Information
Patent Citations
Ion exchangeable, transparent gahnite-spinel glass ceramics with high hardness and modulus
CN111615500A
Cited By
Chemically strengthened microcrystalline glass and preparation thereof
CN121672942A
Chemically strengthened microcrystalline glass and preparation thereof
CN121672942B
Precursor glass for preparing spinel glass ceramics
CN121698567A
Spinel glass ceramic and preparation method thereof
CN121698570A
Spinel microcrystalline glass and preparation method thereof
CN121698570B